Access to new highly potent antileukemia, antiviral and antimalarial agents via hybridization of natural products (homo)egonol, thymoquinone and artemisinin - Capci Karagöz, Aysun; Reiter, Christoph; Seo, Ean-Jeong; Gruber, Lisa; Hahn, Friedrich; Leidenberger, Maria; Klein, Volker; Hampel, Frank; Friedrich, Oliver; Marschall, Manfred; Kappes, Bärbel; Efferth, Thomas; et al. (Bioorganic & Medicinal Chemistry, 2018)
Hybridization of natural products has high potential to further improve their activities and may produce synergistic effects between linked pharmacophores. Here we report synthesis of nine new hybrids of natural products egonol, homoegonol, thymoquinone and artemisinin and evaluation of their activities against P. falciparum 3D7 parasites, human cytomegalovirus, sensitive and multidrug-resistant human leukemia cells. Most of the new hybrids exceed their parent compounds in antimalarial, antiviral and antileukemia activities and in some cases show higher in vitro efficacy than clinically used reference drugs chloroquine, ganciclovir and doxorubicin. Combined, our findings stress the high potency of these hybrids and encourages further use of the hybridization concept in applied pharmacological research.
EVALuna2:35269

A domino reaction strategy for facile and modular construction of synthetically challenging functionalized ortho-fluoroanilines - Grau, Benedikt; Kohlbauer, Sascha; Gu, Yun Gyeong; Hahn, Friedrich; Lösing, Josephine; Wangen, Christina; Stangier, Maximilian; Ackermann, Lutz; Marschall, Manfred; Tsogoeva, Svetlana (Organic Chemistry Frontiers, 2024)
The selective formation of ortho-fluoroanilines, representing versatile intermediates for the pharmaceutical and fine chemical industries, relies to date on, e.g., transition-metal-catalyzed fluorination of azobenzenes, which must be preformed from aniline derivatives. While few efficient methods for aniline synthesis were reported, sustainable, straightforward, and selective synthesis of fluoroanilines, and in particular ortho-fluoroanilines, remains challenging. Herein, we describe a domino approach that involves the simultaneous construction of a benzene ring and the installation of both amine and fluorine groups in a single operation under metal-free conditions, starting from readily available acyclic compounds. The developed atom- and cost-efficient, highly convenient, selective, and environmentally friendly four-step domino process allows the formation of a variety of functionalized ortho-fluoroanilines with yields of up to 80% and bypasses the selectivity issues of transition-metal-catalyzed aniline fluorination reactions. Furthermore, we show that the new domino products can efficiently be utilized to synthesize fluorinated azo dye and (tetrahydro)quinazoline derivatives in a bioactive form, i.e., possessing a first-time proven micromolar antiviral activity and high selectivity (EC50 (HCMV) down to 1.9 ± 0.7 μM, CC50 up to >100 μM), under conventional and/or visible-light mediated conditions.
CRIS-Team Scopus Importer:2024-10-25

A highly potent trimeric derivative of artesunate shows promising treatment profiles in experimental models for congenital HCMV infection in vitro and ex vivo - Jacquet, Chloé; Marschall, Manfred; Andouard, Déborah; El Hamel, Charhazed; Chianea, Thierry; Tsogoeva, Svetlana; Hantz, Sébastien; Alain, Sophie (Antiviral Research, 2020)
CRIS-Team Scopus Importer:2020-02-04

An Antiherpesviral Host-Directed Strategy Based on CDK7 Covalently Binding Drugs: Target-Selective, Picomolar-Dose, Cross-Virus Reactivity - Yu, Dong Hoon; Wagner, Sabrina; Schütz, Martin; Jeon, Yeejin; Seo, Mooyoung; Kim, Jaeseung; Brückner, Nadine; Kicuntod, Jintawee; Tillmanns, Julia; Wangen, Christina; Hahn, Friedrich; Kaufer, Benedikt B.; et al. (Pharmaceutics, 2024)
The repertoire of currently available antiviral drugs spans therapeutic applications against a number of important human pathogens distributed worldwide. These include cases of the pandemic severe acute respiratory coronavirus type 2 (SARS-CoV-2 or COVID-19), human immunodeficiency virus type 1 (HIV-1 or AIDS), and the pregnancy- and posttransplant-relevant human cytomegalovirus (HCMV). In almost all cases, approved therapies are based on direct-acting antivirals (DAAs), but their benefit, particularly in long-term applications, is often limited by the induction of viral drug resistance or side effects. These issues might be addressed by the additional use of host-directed antivirals (HDAs). As a strong input from long-term experiences with cancer therapies, host protein kinases may serve as HDA targets of mechanistically new antiviral drugs. The study demonstrates such a novel antiviral strategy by targeting the major virus-supportive host kinase CDK7. Importantly, this strategy focuses on highly selective, 3D structure-derived CDK7 inhibitors carrying a warhead moiety that mediates covalent target binding. In summary, the main experimental findings of this study are as follows: (1) the in vitro verification of CDK7 inhibition and selectivity that confirms the warhead covalent-binding principle (by CDK-specific kinase assays), (2) the highly pronounced antiviral efficacies of the hit compounds (in cultured cell-based infection models) with half-maximal effective concentrations that reach down to picomolar levels, (3) a particularly strong potency of compounds against strains and reporter-expressing recombinants of HCMV (using infection assays in primary human fibroblasts), (4) additional activity against further herpesviruses such as animal CMVs and VZV, (5) unique mechanistic properties that include an immediate block of HCMV replication directed early (determined by Western blot detection of viral marker proteins), (6) a substantial drug synergism in combination with MBV (measured by a Loewe additivity fixed-dose assay), and (7) a strong sensitivity of clinically relevant HCMV mutants carrying MBV or ganciclovir resistance markers. Combined, the data highlight the huge developmental potential of this host-directed antiviral targeting concept utilizing covalently binding CDK7 inhibitors.
CRIS-Team Scopus Importer:2025-02-04
Keywords: covalently CDK7-binding warheads; cyclin-dependent kinase 7 (CDK7); cytomegalovirus infection; distinct mode of drug targeting; drug synergism with maribavir; major human pathogen; novel antiherpesviral strategy; picomolar effective concentrations; virus-supportive host kinases

An antiviral targeting strategy based on the inducible interference with cytomegalovirus nuclear egress complex - Kicuntod, Jintawee; Häge, Sigrun; Lösing, Josephine; Kopar, Serli; Muller, Yves; Marschall, Manfred (Antiviral Research, 2023)
The nucleocytoplasmic capsid egress of herpesviruses like the human cytomegalovirus (HCMV) is based on a uniquely regulated process. The core nuclear egress complex (NEC) of HCMV, represented by the pUL50–pUL53 heterodimer, is able to oligomerize and thus to build hexameric lattices. Recently, we and others validated the NEC as a novel target for antiviral strategies. So far, the experimental targeting approaches included the development of NEC-directed small molecules, cell-penetrating peptides and NEC-directed mutagenesis. Our postulate states that an interference with the hook-into-groove interaction of pUL50–pUL53 prevents NEC formation and strictly limits viral replication efficiency. Here, we provide an experimental proof-of-concept of the antiviral strategy: the inducible intracellular expression of a NLS-Hook-GFP construct exerted a pronounced level of antiviral activity. The data provide evidence for the following points: (i) generation of a primary fibroblast population with inducible NLS-Hook-GFP expression showed nuclear localization of the construct, (ii) interaction between NLS-Hook-GFP and the viral core NEC was found specific for cytomegaloviruses but not for other herpesviruses, (iii) construct overexpression exerted a strong antiviral activity against three strains of HCMV, (iv) confocal imaging demonstrated the interference with NEC nuclear rim formation in HCMV-infected cells, and (v) quantitative nuclear egress assay confirmed the block of viral nucleocytoplasmic transition and, consequently, an inhibitory effect onto viral cytoplasmic virion assembly complex (cVAC). Combined, data confirmed that the specific interference with protein-protein interaction of the HCMV core NEC represents an efficient antiviral targeting strategy.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Antiviral proof-of-concept; Cytomegalovirus infection; Efficient interference with viral replication; Hook-into-groove principle; Inducible NLS-Hook-GFP expression; Major human pathogen; Novel drug targeting options; Nuclear egress-based antiviral strategy

A novel CDK7 inhibitor of the Pyrazolotriazine class exerts broad-spectrum antiviral activity at nanomolar concentrations - Hutterer, Corina; Eickhoff, Jan; Milbradt, Jens; Korn, Klaus; Zeitträger, Isabel; Bahsi, Hanife; Wagner, Sabrina; Zischinsky, Gunther; Wolf, Alexander; Degenhart, Carsten; Unger, Anke; Baumann, Matthias; et al. (Antimicrobial Agents and Chemotherapy, 2015)
Protein kinases represent central and multifunctional regulators of a balanced virus-host interaction. Cyclin-dependent protein kinase 7 (CDK7) plays crucial regulatory roles in cell cycle and transcription, both connected with the replication of many viruses. Previously, we developed a CDK7 inhibitor, LDC4297, that inhibits CDK7 in vitro in the nano-picomolar range. Novel data from a kinome-wide evaluation (>330 kinases profiled in vitro) demonstrate a kinase selectivity. Importantly, we provide first evidence for the antiviral potential of the CDK7 inhibitor LDC4297, i.e., in exerting a block of the replication of human cytomegalovirus (HCMV) in primary human fibroblasts at nanomolar concentrations (50% effective concentration, 24.5 ± 1.3 nM). As a unique feature compared to approved antiherpesviral drugs, inhibition occurred already at the immediate-early level of HCMV gene expression. The mode of antiviral action was considered multifaceted since CDK7-regulated cellular factors that are supportive of HCMV replication were substantially affected by the inhibitors. An effect of LDC4297 was identified in the interference with HCMV-driven inactivation of retinoblastoma protein (Rb), a regulatory step generally considered a hallmark of herpesviral replication. In line with this finding, a broad inhibitory activity of the drug could be demonstrated against a selection of human and animal herpesviruses and adenoviruses, whereas other viruses only showed intermediate drug sensitivity. Summarized, the CDK7 inhibitor LDC4297 is a promising candidate for further antiviral drug development, possibly offering new options for a comprehensive approach to antiviral therapy.
EVALuna2:8274

Anti-SARS-CoV-2 Inhibitory Profile of New Quinoline Compounds in Cell Culture-Based Infection Models - Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2021)
The presently ongoing pandemic of human SARS-CoV-2 infections (COVID-19) presents an enormous challenge in surveillance, vaccine and antiviral drug development. Here we report the synthesis of new bioactive quinoline-morpholine hybrid compounds and their virological evaluation, which proves pronounced cell culture-based inhibitory profile against SARS-CoV-2. Thus, selected quinoline compounds may suggest specific hit-to-lead development.
CRIS-Team WoS Importer:2022-01-07

Antiviral effects of artesunate on JC polyomavirus replication in COS-7 cells - Sharma, Biswa Nath; Marschall, Manfred; Rinaldo, Christine Hanssen (Antimicrobial Agents and Chemotherapy, 2014)
The human JC polyomavirus (JCPyV) causes the fatal demyelinating disease progressive multifocal leukoencephalopathy (PML). A growing number of patients with induced or acquired immunosuppression are at risk for infection, and no effective antiviral therapy is presently available. The widely used antimalarial drug artesunate has shown broad antiviral activity in vitro but limited clinical success. The aim of this study was to investigate the effect of artesunate on JCPyV replication in vitro. The permissivity for JCPyV MAD-4 was first compared in four cell lines, and the monkey kidney cell line COS-7 was selected. Artesunate caused a concentration-dependent decrease in the extracellular JCPyV DNA load 96 h postinfection, with a 50% effective concentration (EC50) of 2.9 ?M. This effect correlated with a decreased expression of capsid protein VP1 and a reduced release of infectious viral progeny. For concentrations of <20 ?M, transient reductions in cellular DNA replication and proliferation were seen, while for higher concentrations, some cytotoxicity was detected. A selective index of 16.6 was found when cytotoxicity was calculated based on cellular DNA replication in the mock-infected cells, but interestingly, cellular DNA replication in the JCPyV-infected cells was more strongly affected. In conclusion, artesunate is efficacious in inhibiting JCPyV replication at micromolar concentrations, which are achievable in plasma. The inhibition at EC50 probably reflects an effect on cellular proteins and involves transient cytostatic effects. Our results, together with the favorable distribution of the active metabolite dihydroartemisinin to the central nervous system, suggest a potential use for artesunate in patients with PML.
EVALuna2:8233

Antiviral effects of artesunate on polyomavirus BK replication in primary human kidney cells - Sharma, Biswa Nath; Marschall, Manfred; Henriksen, Stian; Rinaldo, Christine Hanssen (Antimicrobial Agents and Chemotherapy, 2014)
Polyomavirus BK (BKV) causes polyomavirus-associated nephropathy (PyVAN) and hemorrhagic cystitis (PyVHC) in renal and bone marrow transplant patients, respectively. Antiviral drugs with targeted activity against BKV are lacking. Since the antimalarial drug artesunate was recently demonstrated to have antiviral activity, the possible effects of artesunate on BKV replication in human primary renal proximal tubular epithelial cells (RPTECs), the host cells in PyVAN, were explored. At 2 h postinfection (hpi), RPTECs were treated with artesunate at concentrations ranging from 0.3 to 80 ?M. After one viral replication cycle (approximately 72 hpi), the loads of extracellular BKV DNA, reflecting viral progeny production, were reduced in a concentration-dependent manner. Artesunate at 10 ?M reduced the extracellular BKV load by 65%; early large T antigen mRNA and protein expression by 30% and 75%, respectively; DNA replication by 73%; and late VP1 mRNA and protein expression by 47% and 64%, respectively. Importantly, the proliferation of RPTECs was also inhibited in a concentration-dependent manner. At 72 hpi, artesunate at 10 ?M reduced cellular DNA replication by 68% and total metabolic activity by 47%. Cell impedance and lactate dehydrogenase measurements indicated a cytostatic but not a cytotoxic mechanism. Flow cytometry and 5-ethynyl-2'-deoxyuridine incorporation revealed a decreased number of cells in S phase and suggested cell cycle arrest in G0 or G2 phase. Both the antiproliferative and antiviral effects of artesunate at 10 ?M were reversible. Thus, artesunate inhibits BKV replication in RPTECs in a concentration-dependent manner by inhibiting BKV gene expression and genome replication. The antiviral mechanism appears to be closely connected to cytostatic effects on the host cell, underscoring the dependence of BKV on host cell proliferative functions.
EVALuna2:8202

Antiviral Strategies Using Natural Source-Derived Sulfated Polysaccharides in the Light of the COVID-19 Pandemic and Major Human Pathogenic Viruses - Ray, Bimalendu; Ali, Imran; Jana, Subrata; Mukherjee, Shuvam; Pal, Saikat; Ray, Sayani; Schütz, Martin; Marschall, Manfred (Viruses, 2022)
Only a mere fraction of the huge variety of human pathogenic viruses can be targeted by the currently available spectrum of antiviral drugs. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has highlighted the urgent need for molecules that can be deployed quickly to treat novel, developing or re-emerging viral infections. Sulfated polysaccharides are found on the surfaces of both the susceptible host cells and the majority of human viruses, and thus can play an important role during viral infection. Such polysaccharides widely occurring in natural sources, specifically those converted into sulfated varieties, have already proved to possess a high level and sometimes also broad-spectrum antiviral activity. This antiviral potency can be determined through multifold molecular pathways, which in many cases have low profiles of cytotoxicity. Consequently, several new polysaccharide-derived drugs are currently being investigated in clinical settings. We reviewed the present status of research on sulfated polysaccharide-based antiviral agents, their structural characteristics, structure–activity relationships, and the potential of clinical application. Furthermore, the molecular mechanisms of sulfated polysaccharides involved in viral infection or in antiviral activity, respectively, are discussed, together with a focus on the emerging methodology contributing to polysaccharide-based drug development.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Antiviral activities and mechanisms; Antiviral efficacy; Drug structure-activity relationship; Emerging viral infections; Heparin mimetics; In vivo studies; Major human pathogenic viruses; Sulfated polysaccharides; Virus entry as a target

A Peptide Inhibitor of the Human Cytomegalovirus Core Nuclear Egress Complex - Alkhashrom, Sewar; Kicuntod, Jintawee; Stillger, Katharina; Luetzenburg, Tamara; Anzenhofer, Christian; Neundorf, Ines; Marschall, Manfred; Eichler, Jutta (Pharmaceuticals, 2022)
The replication of human cytomegalovirus (HCMV) involves a process termed nuclear egress, which enables translocation of newly formed viral capsids from the nucleus into the cytoplasm. The HCMV core nuclear egress complex (core NEC), a heterodimer of viral proteins pUL50 and pUL53, is therefore considered a promising target for new antiviral drugs. We have recently shown that a 29-mer peptide presenting an N-terminal alpha-helical hook-like segment of pUL53, through which pUL53 interacts with pUL50, binds to pUL50 with high affinity, and inhibits the pUL50–pUL53 interaction in vitro. Here, we show that this peptide is also able to interfere with HCMV infection of cells, as well as with core NEC formation in HCMV-infected cells. As the target of the peptide, i.e., the pUL50–pUL53 interaction, is localized at the inner nuclear membrane of the cell, the peptide had to be equipped with translocation moieties that facilitate peptide uptake into the cell and the nucleus, respectively. For the resulting fusion peptide (NLS-CPP-Hook), specific cellular and nuclear uptake into HFF cells, as well as inhibition of infection with HCMV, could be demonstrated, further substantiating the HCMV core NEC as a potential antiviral target.
CRIS-Team Scopus Importer:2022-10-07
Keywords: antiviral peptide; cell penetrating peptide (CPP); cellular uptake; human cytomegalovirus; nuclear egress complex (NEC); nuclear localization signal (NLS); nuclear uptake

A placental specific miRNA miR-517a-3p exerts anti-human cytomegalovirus activity - Hamilton, Stuart T.; Hahn, Friedrich; Sonntag, Eric; Marschall, Manfred; Rawlinson, William D. (Placenta, 2021)
Human cytomegalovirus congenital infection is the leading non-genetic cause of fetal malformation in developed countries. There are currently no safe antivirals for use during pregnancy. Placental trophoblast cells specifically secrete exosomes containing miRNA from the chromosome 19 miRNA cluster (C19MC) which confer viral resistance to recipient cells. We show the highly expressed C19MC miRNA miR-517a-3p inhibits HCMV replication and viral protein expression in both fibroblast and trophoblast cell cultures (71.6% and 50.4% inhibition of HCMV DNA at 7 days post infection respectively; p < 0.05). This naturally occurring molecule has potential for opening-up antiviral therapeutic strategies for pregnancy.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Antivirals; Congenital infection; Cytomegalovirus; Placenta; Pregnancy

A quantitative nuclear egress assay to investigate the nucleocytoplasmic capsid release of human cytomegalovirus - Häge, Sigrun; Horsch, Deborah; Stilp, Anne Charlotte; Kicuntod, Jintawee; Müller, Regina; Hamilton, Stuart T.; Egilmezer, Ece; Rawlinson, William D.; Stamminger, Thomas; Sonntag, Eric; Marschall, Manfred (Journal of Virological Methods, 2020)
Nuclear egress is a rate-limiting step of herpesviral replication, restricting the nucleocytoplasmic transport of viral capsids. The process is regulated by two viral nuclear egress proteins (core NEC pUL50-pUL53), which recruit additional cellular and viral proteins. The multicomponent NEC mediates disassembly of the nuclear lamina barrier and the docking of nuclear capsids. The quantitation of nuclear egress has been accomplished by electron microscopic analysis, but is generally hampered by the low number of detectable cytoplasmic capsids. A newly established method for the quantitation of viral nuclear egress improves the characterization of viral mutants, host cell permissiveness and antiviral drug efficacy. In this study, various strains of human cytomegalovirus (HCMV) were used to measure the replication efficiencies in primary human fibroblasts, applying methods of cell fractionation, DNase digestion, sucrose cushions and quantitative PCR. Several stages of optimization led to a reliable quantitative assay that allowed the characterization of viral nuclear egress efficacy. Using this assay, recovery of the nuclear egress of a NEC-defective HCMV mutant was quantitatively assessed by applying an inducible NEC-expressing fibroblast culture for trans-complementation. This novel assay system can be further used to accurately quantitate and characterize the functionality of nuclear egress of HCMV or other herpesviruses.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Capsid-Release; Cytomegalovirus; Fractionation; genome-specific-qPCR; Nuclear egress; Quantitative assay

Artesunate derivative TF27 inhibits replication and pathogenesis of an oncogenic avian alphaherpesvirus - Bertzbach, Luca D.; Conradie, Andelé M.; Hahn, Friedrich; Wild, Markus; Marschall, Manfred; Kaufer, Benedikt B. (Antiviral Research, 2019)
Nucleoside analogues have been the cornerstone of clinical treatment of herpesvirus infections since the 1970s. However, severe side effects and emergence of drug resistant viruses raise the need for alternative treatment options. We recently investigated the broad and strong antiherpesviral activity of the optimized artesunate derivative TF27 in vitro. TF27 efficiently inhibited replication of the highly oncogenic Marek's disease virus (MDV), a virus that infects chickens, causes deadly lymphomas and threatens poultry populations worldwide. In this study, we used this natural virus-host model for herpesvirus-induced cancer by infecting chickens with MDV, and evaluated the protective efficacy of TF27 and the nucleoside analogue valganciclovir (VGCV) on virus replication and tumorigenesis. We could demonstrate that both drugs reduced viral load in the blood and prevented tumor development in a large portion of the animals. Antiviral treatment also had a positive impact on body weight gain, while no negative compound-associated side effects were observed. This research provides the first evidence that the artesunate derivative TF27 and VGCV can be used in avian species and that they inhibit MDV replication and tumorigenesis. In addition, our study paves the way for promising approaches in future antiherpesviral drug development.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Artesunate; Artesunate derivative; Experimental antiviral drug; Herpesviral in vivo models; Indirect host-targeted antivirals; Marek's disease virus; NF-κB signaling inhibition

Artesunate-derived monomeric, dimeric and trimeric experimental drugs - Their unique mechanistic basis and pronounced antiherpesviral activity - Hahn, Friedrich; Fröhlich, Tony; Frank, Theresa; Bertzbach, Luca D.; Kohrt, Stephan; Kaufer, Benedikt B.; Stamminger, Thomas; Tsogoeva, Svetlana; Marschall, Manfred (Antiviral Research, 2018)
Human cytomegalovirus (HCMV) is a major human pathogen and is associated with severe pathology, such as life-threatening courses of infection in immunocompromised individuals and neonates. Currently, antiviral therapy is still hampered by a considerable toxicity of the available drugs and induction of viral resistance. Recently, we and others reported the very potent antiviral activity of the broad antiinfective drug artesunate in vitro and in vivo. Here, we investigated further optimized analogs including monomeric, dimeric and trimeric derivatives belonging to this highly interesting chemical group of experimental drugs (sesquiterpenes/trioxanes) and compared these to the previously identified trimeric artesunate compound TF27. We could demonstrate that (i) seven of the eight investigated monomeric, dimeric and trimeric artesunate derivatives, i.e. TF79, TF85, TF87, TF93.2.4, TF111, TF57a and TF57ab, exerted a strong anti-HCMV activity in primary human fibroblasts, (ii) the EC50 values ranged in the low to sub-micromolar concentrations and indicated a higher antiviral potency than the recently described artesunate analogs, (iii) one trimeric compound, TF79, showed a very promising EC50 of 0.03 +/- 0.00 mu M, which even exceled the antiviral potency of TF27 (EC50 0.04 +/- 0.01 mu M), (iv) levels of cytotoxicity (quantitative measurement of lactate dehydrogenase release) were low in a range between 100 and 30 mu M and thus different from antiviral concentrations, (v) an analysis of protein expression levels indicated a potent block of viral protein expression, and (vi) data from a NF-kappa B reporter cell system strongly suggested that these compounds share the same antiviral mechanism. Taken together, our data on these novel compounds strongly encourages our earlier concept on the oligomerization and hybridization of artesunate analogs, providing an excellent platform for the generation of antiherpesviral drugs.
EVALuna2:35282

Assessment of Covalently Binding Warhead Compounds in the Validation of the Cytomegalovirus Nuclear Egress Complex as an Antiviral Target - Tillmanns, Julia; Häge, Sigrun; Borst, Eva Maria; Wardin, Julia; Eickhoff, Jan; Klebl, Bert; Wagner, Sabrina; Wangen, Christina; Hahn, Friedrich; Socher, Eileen; Marschall, Manfred (Cells, 2023)
Herpesviral nuclear egress is a regulated process of viral capsid nucleocytoplasmic release. Due to the large capsid size, a regular transport via the nuclear pores is unfeasible, so that a multistage-regulated export pathway through the nuclear lamina and both leaflets of the nuclear membrane has evolved. This process involves regulatory proteins, which support the local distortion of the nuclear envelope. For human cytomegalovirus (HCMV), the nuclear egress complex (NEC) is determined by the pUL50–pUL53 core that initiates multicomponent assembly with NEC-associated proteins and capsids. The transmembrane NEC protein pUL50 serves as a multi-interacting determinant that recruits regulatory proteins by direct and indirect contacts. The nucleoplasmic core NEC component pUL53 is strictly associated with pUL50 in a structurally defined hook-into-groove complex and is considered as the potential capsid-binding factor. Recently, we validated the concept of blocking the pUL50–pUL53 interaction by small molecules as well as cell-penetrating peptides or an overexpression of hook-like constructs, which can lead to a pronounced degree of antiviral activity. In this study, we extended this strategy by utilizing covalently binding warhead compounds, originally designed as binders of distinct cysteine residues in target proteins, such as regulatory kinases. Here, we addressed the possibility that warheads may likewise target viral NEC proteins, building on our previous crystallization-based structural analyses that revealed distinct cysteine residues in positions exposed from the hook-into-groove binding surface. To this end, the antiviral and NEC-binding properties of a selection of 21 warhead compounds were investigated. The combined findings are as follows: (i) warhead compounds exhibited a pronounced anti-HCMV potential in cell-culture-based infection models; (ii) computational analysis of NEC primary sequences and 3D structures revealed cysteine residues exposed to the hook-into-groove interaction surface; (iii) several of the active hit compounds exhibited NEC-blocking activity, as shown at the single-cell level by confocal imaging; (iv) the clinically approved warhead drug ibrutinib exerted a strong inhibitory impact on the pUL50–pUL53 core NEC interaction, as demonstrated by the NanoBiT assay system; and (v) the generation of recombinant HCMV ∆UL50-ΣUL53, allowing the assessment of viral replication under conditional expression of the viral core NEC proteins, was used for characterizing viral replication and a mechanistic evaluation of ibrutinib antiviral efficacy. Combined, the results point to a rate-limiting importance of the HCMV core NEC for viral replication and to the option of exploiting this determinant by the targeting of covalently NEC-binding warhead compounds.
Created from Fastlane, Scopus look-up
Keywords: antiviral targeting based on NEC 3D structures; conditional expression of viral core NEC proteins; covalently binding warhead compounds; human cytomegalovirus; nuclear egress complex (NEC); pronounced NEC-directed antiviral activity; regulation of viral replication

Autofluorescent Artemisinin-Benzimidazole Hybrids via Organo-Click Reaction: Study of Antiviral Properties and Mode of Action in Living Cells - Herrmann, Lars; Hahn, Friedrich; Grau, Benedikt; Wild, Markus; Niesar, Aischa; Wangen, Christina; Kataev, Evgeny; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2023)
Drug modification by a fluorescent label is a common tool for studying its mechanism of action with fluorescence microscopy techniques. However, the attachment of a fluorescent label can significantly alter the polarity, solubility, and biological activity of the investigated drug, and, as a result, the studied mechanism of action can be misrepresented. Therefore, developing efficient drugs, which are inherently fluorescent and can be tracked directly in the cell is highly favorable. Here an easy formation of fluorescent hybrid drugs is presented, generated by a combination of two readily available non-fluorescent pharmacophores via a non-cleavable linker using a Ramachary-Bressy-Wang organocatalyzed azide-carbonyl [3+2] cycloaddition (organo-click) reaction. All newly prepared fluorescent compounds showed strong anti-HCMV activity (EC50 down to 0.07±0.00 μM), thus presenting a very promising drug developmental basis compared to the approved drug ganciclovir (EC50 2.60±0.50 μM). Remarkably, in vitro fluorescent imaging investigation of new compounds revealed induced changes in mitochondrial structures, which is a phenotypical hallmark of antiviral activity. This approach opens up new vistas for the easy formation of potent fluorescent drugs from readily available non-fluorescent parent compounds and might facilitate insight into their mode of action in living cells, avoiding the requirement of linkage to external fluorescent markers.
CRIS-Team Scopus Importer:2023-09-08
Keywords: artemisinin-benzimidazole hybrids; autofluorescent antivirals; confocal microscopy; organo-click reaction; [3+2] cycloaddition

Begomoviral Movement Protein Effects in Human and Plant Cells: Towards New Potential Interaction Partners - Krapp, Susanna; Schuy, Christian; Greiner, Eva; Stephan, Irina; Alberter, Barbara; Funk, Christina; Marschall, Manfred; Wege, Christina; Bailer, Susanne M.; Kleinow, Tatjana; Krenz, Bjoern (Viruses, 2017)
Geminiviral single-stranded circular DNA genomes replicate in nuclei so that the progeny DNA has to cross both the nuclear envelope and the plasmodesmata for systemic spread within plant tissues. For intra- and intercellular transport, two proteins are required: a nuclear shuttle protein (NSP) and a movement protein (MP). New characteristics of ectopically produced Abutilon mosaic virus (AbMV) MP (MPAbMV), either authentically expressed or fused to a yellow fluorescent protein or epitope tags, respectively, were determined by localization studies in mammalian cell lines in comparison to plant cells. Wild-type MPAbMVand the distinct MPAbMV: reporter protein fusions appeared as curled threads throughout mammalian cells. Co-staining with cytoskeleton markers for actin, intermediate filaments, or microtubules identified these threads as re-organized microtubules. These were, however, not stabilized by the viral MP, as demonstrated by nocodazole treatment. The MP of a related bipartite New World begomovirus, Cleome leaf crumple virus (ClLCrV), resulted in the same intensified microtubule bundling, whereas that of a nanovirus did not. The C-terminal section of MPAbMV, i.e., the protein's oligomerization domain, was dispensable for the effect. However, MP expression in plant cells did not affect the microtubules network. Since plant epidermal cells are quiescent whilst mammalian cells are proliferating, the replication-associated protein RepAbMVprotein was then co-expressed with MPAbMVto induce cell progression into S-phase, thereby inducing distinct microtubule bundling without MP recruitment to the newly formed threads. Co-immunoprecipitation of MPAbMVin the presence of RepAbMV, followed by mass spectrometry identified potential novel MPAbMV-host interaction partners: the peptidyl-prolyl cis-trans isomerase NIMA-interacting 4 (Pin4) and stomatal cytokinesis defective 2 (SCD2) proteins. Possible roles of these putative interaction partners in the begomoviral life cycle and cytoskeletal association modes are discussed.
EVALuna2:33750

Chemically sulfated polysaccharides from natural sources: Assessment of extraction-sulfation efficiencies, structural features and antiviral activities - Mukherjee, Shuvam; Ghosh, Kanika; Hahn, Friedrich; Wangen, Christina; Strojan, Hanife; Müller, Regina; Anand, Namrata; Ali, Imran; Bera, Kaushik; Ray, Bimalendu; Hutterer, Corina; Marschall, Manfred; et al. (International Journal of Biological Macromolecules, 2019)
The provisioning of compound libraries with a high degree of diversity and attractive pharmacological properties is a limiting step in drug development. This study reports the production of highly bioactive sulfated polysaccharides, originally present in a nonsulfated, dormant state in natural sources, and demonstrates their antiviral activity (human cytomegalovirus EC50 values of 2.34–7.77 μg/mL) at a low degree of cytotoxicity. Furthermore, data strongly suggested the inhibition of virus entry as the main mode of antiviral action. Remarkably, the utilized oleum-DMF reagent was able to generate a range of sulfated polysaccharides from various natural sources, possessing varying saccharide compositions, degrees of sulfation (0.4–1.7) and molecular masses (38–94,000 g/mol). Typically, in a matter of minutes, this reagent not only solubilized polysaccharides but also chemically converted their hydroxyl functionality into sulfates. The most active sulfated polysaccharide (EC50 of 2.62 μg/mL) proved to be a 94,000 g/mol branched glucan with sulfates at C-6/C-3,6/C-2,3,6 positions. In conclusion, the important determinants of such compounds' antiviral activity are: (i) degree of sulfation, (ii) molecular mass and (iii) structural features. Thus, our approach offers a huge prospect for the improvement of natural source-derived libraries based on biologically active polysaccharides with diversified chemical profiles.
CRIS-Team Scopus Importer:2019-06-28
Keywords: Antiviral activities; Functionalization; Natural products; Polysaccharides; Structural features

Combinatorial drug treatments reveal promising anticytomegaloviral profiles for clinically relevant pharmaceutical kinase inhibitors (PKIs) - Wild, Markus; Kicuntod, Jintawee; Seyler, Lisa; Wangen, Christina; Bertzbach, Luca D.; Conradie, Andelé M.; Kaufer, Benedikt B.; Wagner, Sabrina; Michel, Detlef; Eickhoff, Jan; Tsogoeva, Svetlana; Bäuerle, Tobias; et al. (International Journal of Molecular Sciences, 2021)
Human cytomegalovirus (HCMV) is a human pathogenic herpesvirus associated with a variety of clinical symptoms. Current antiviral therapy is not always effective, so that improved drug classes and drug-targeting strategies are needed. Particularly host-directed antivirals, including pharmaceutical kinase inhibitors (PKIs), may help to overcome problems of drug resistance. Here, we focused on utilizing a selection of clinically relevant PKIs and determined their anticytomegaloviral efficacies. Particularly, PKIs directed to host or viral cyclin-dependent kinases, i.e., abemaciclib, LDC4297 and maribavir, exerted promising profiles against human and murine cytomegaloviruses. The anti-HCMV in vitro activity of the approved anti-cancer drug abemaciclib was confirmed in vivo using our luciferase-based murine cytomegalovirus (MCMV) animal model in immunocompetent mice. To assess drug combinations, we applied the Bliss independence checkerboard and Loewe additivity fixed-dose assays in parallel. Results revealed that (i) both affirmative approaches provided valuable information on anti-CMV drug efficacies and interactions, (ii) the analyzed combinations comprised additive, synergistic or antagonistic drug interactions consistent with the drugs’ antiviral mode-of-action, (iii) the selected PKIs, especially LDC4297, showed promising inhibitory profiles, not only against HCMV but also other α-, β-and γ-herpesviruses, and specifically, (iv) the combination treatment with LDC4297 and maribavir revealed a strong synergism against HCMV, which might open doors towards novel clinical options in the near future. Taken together, this study highlights the potential of therapeutic drug combinations of current developmental/preclinical PKIs.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Activity in vitro and in vivo; Antiviral drugs; Combinatorial drug analyses; Human cytomegalovirus; New synergistic combinations; Pharmaceutical kinase inhibitors (PKIs)

Combined Treatment with Host-Directed and Anticytomegaloviral Kinase Inhibitors: Mechanisms, Synergisms and Drug Resistance Barriers. - Wild, Markus; Karner, Dubravka; Eickhoff, Jan; Wagner, Sabrina; Kicuntod, Jintawee; Chang, William; Barry, Peter; Jonjić, Stipan; Lenac Roviš, Tihana; Marschall, Manfred (Pharmaceutics, 2023)
Despite the availability of currently approved antiviral drugs, infections with human cytomegalovirus (HCMV) still cause clinically challenging, sometimes life-threatening situations. There is an urgent need for enhanced anti-HCMV drugs that offer improved efficacy, reduced dosages and options for long-term treatment without risk of the development of viral drug resistance. Recently, we reported the pronounced anti-HCMV efficacy of pharmacological inhibitors of cyclin-dependent kinases (CDKs), in particular, the potential of utilizing drug synergies upon combination treatment with inhibitors of host CDKs and the viral CDK-like kinase pUL97 (vCDK/pUL97). Here, we expand this finding by further assessing the in vitro synergistic antiviral interaction between vCDK and CDK inhibitors towards HCMV as well as non-human cytomegaloviruses. An extension of this synergy approach was achieved in vivo by using the recombinant MCMV-UL97/mouse model, confirming the high potential of combination treatment with the clinically approved vCDK inhibitor maribavir (MBV) and the developmental CDK7 inhibitor LDC4297. Moreover, mechanistic aspects of this synergistic drug combination were illustrated on the levels of intracellular viral protein transport and viral genome replication. The analysis of viral drug resistance did not reveal resistance formation in the case of MBV + LDC4297 combination treatment. Spanning various investigational levels, these new results strongly support our concept, employing the great potential of anti-HCMV synergistic drug treatment.
EVALuna2:545511

'Come together'-The Regulatory Interaction of Herpesviral Nuclear Egress Proteins Comprises Both Essential and Accessory Functions - Häge, Sigrun; Marschall, Manfred (Cells, 2022)
Herpesviral nuclear egress is a fine-tuned regulatory process that defines the nucleocytoplasmic release of viral capsids. Nuclear capsids are unable to traverse via nuclear pores due to the fact of their large size; therefore, herpesviruses evolved to develop a vesicular transport pathway mediating the transition across the two leaflets of the nuclear membrane. The entire process involves a number of regulatory proteins, which support the local distortion of the nuclear envelope. In the case of the prototype species of beta-Herpesvirinae, the human cytomegalovirus (HCMV), the nuclear egress complex (NEC) is determined by the core proteins pUL50 and pUL53 that oligomerize, form capsid docking lattices and mediate multicomponent assembly with NEC-associated viral and cellular proteins. The NEC-binding principle is based on the hook-into-groove interaction through an N-terminal hook-like pUL53 protrusion that embraces an alpha-helical pUL50 binding groove. Thus far, the function and characteristics of herpesviral core NECs have been well studied and point to the groove proteins, such as pUL50, as the multi-interacting, major determinants of NEC formation and egress. This review provides closer insight into (i) sequence and structure conservation of herpesviral core NEC proteins, (ii) experimentation on cross-viral core NEC interactions, (iii) the essential functional roles of hook and groove proteins for viral replication, (iv) an establishment of assay systems for NEC-directed antiviral research and (v) the validation of NEC as putative antiviral drug targets. Finally, this article provides new insights into the conservation, function and antiviral targeting of herpesviral core NEC proteins and, into the complex regulatory role of hook and groove proteins during the assembly, egress and maturation of infectious virus.
CRIS-Team WoS Importer:2022-06-24
Keywords: herpesviruses; human cytomegalovirus; regulation of viral replication; nuclear egress complex (NEC); NEC hook and groove proteins; functional properties; conditional expression; specialized functional aspects; efficiency of virus production; antiviral drug target

Crystal structure of the human cytomegalovirus pUL50-pUL53 core nuclear egress complex provides insight into a unique assembly scaffold for virus-host protein interactions - Walzer, Sascha; Egerer-Sieber, Claudia; Sticht, Heinrich; Sevvana, Madhumati; Hohl, Katharina; Milbradt, Jens; Muller, Yves; Marschall, Manfred (Journal of Biological Chemistry, 2015)
Nuclear replication of cytomegalovirus relies on elaborate mechanisms of nucleocytoplasmic egress of viral particles. Thus, the role of two essential and conserved viral nuclear egress proteins, pUL50 and pUL53, is pivotal. pUL50 and pUL53 heterodimerize and form a core nuclear egress complex (NEC), which is anchored to the inner nuclear membrane and provides a scaffold for the assembly of a multimeric viral-cellular NEC. Here, we report the crystal structure of the pUL50-pUL53 heterodimer (amino acids 1-175 and 50-292, respectively) at 2.44 Å resolution. Both proteins adopt a globular fold with mixed α and β secondary structure elements. pUL53-specific features include a zinc-binding site and a hook-like N-terminal extension, the latter representing a hallmark element of the pUL50-pUL53 interaction. The hook-like extension (amino acids 59-87) embraces pUL50 and contributes 1510 Å to the total interface area (1880Å). The pUL50 structure overall resembles the recently published NMR structure of the murine cytomegalovirus homolog pM50 but reveals a considerable repositioning of the very C-terminal α-helix of pUL50 upon pUL53 binding. pUL53 shows structural resemblance with the GHKL domain of bacterial sensory histidine kinases. A close examination of the crystal structure indicates partial assembly of pUL50-pUL53 heterodimers to hexameric ring-like structures possibly providing additional scaffolding opportunities for NEC. In combination, the structural information on pUL50-pUL53 considerably improves our understanding of the mechanism of HCMV nuclear egress. It may also accelerate the validation of the NEC as a unique target for developing a novel type of antiviral drug and improved options of broad-spectrum antiherpesviral therapy.

Cyclin-Dependent Kinase 8 Represents a Positive Regulator of Cytomegalovirus Replication and a Novel Host Target for Antiviral Strategies - Obergfäll, Debora; Wild, Markus; Sommerer, Mona; Barillas Dahm, Malena; Kicuntod, Jintawee; Tillmanns, Julia; Kögler, Melanie; Lösing, Josephine; Dhotre, Kishore; Müller, Regina; Wangen, Christina; Wagner, Sabrina; et al. (Pharmaceutics, 2024)
Background. Cyclin-dependent kinase 8 (CDK8) is a multifaceted regulator and represents a catalytic component of the transcriptional Mediator complex. CDK8 activity, on the one hand, increases transcriptional elongation by the recruitment of Mediator/super elongation complexes, but, on the other hand, negatively regulates CDK7-controlled transcriptional initiation through inactivating cyclin H phosphorylation. Recently, these combined properties of CDK8 have also suggested its rate-limiting importance for herpesviral replication. Objectives. In this paper, we focused on human cytomegalovirus (HCMV) and addressed the question of whether the pharmacological inhibition or knock-down of CDK8 may affect viral replication efficiency in cell culture models. Methods. A number of human and animal herpesviruses, as well as non-herpesviruses, were used to analyze the importance of CDK8 for viral replication in cell culture models, and to assess the antiviral efficacy of CDK8 inhibitors. Results. Using clinically relevant CDK8 inhibitors (CCT-251921, MSC-2530818, and BI-1347), HCMV replication was found strongly reduced even at nanomolar drug concentrations. The EC50 values were consistent for three different HCMV strains (i.e., AD169, TB40, and Merlin) analyzed in two human cell types (i.e., primary fibroblasts and astrocytoma cells), and the drugs comprised a low level of cytotoxicity. The findings highlighted the following: (i) the pronounced in vitro SI values of anti-HCMV activity obtained with CDK8 inhibitors; (ii) a confirmation of the anti-HCMV efficacy by CDK8–siRNA knock-down; (iii) a CDK8-dependent reduction in viral immediate early, early, and late protein levels; (iv) a main importance of CDK8 for viral late-stage replication; (v) several mechanistic aspects, which point to a strong impact on viral progeny production and release, but a lack of CDK8 relevance for viral entry or nuclear egress; (vi) a significant anti-HCMV drug synergy for combinations of inhibitors against host CDK8 and the viral kinase vCDK/pUL97 (maribavir); (vii) finally, a broad-spectrum antiviral activity, as seen for the comparison of selected α-, β-, γ-, and non-herpesviruses. Conclusions. In summary, these novel data provide evidence for the importance of CDK8 as a positive regulator of herpesviral replication efficiency, and moreover, suggest its exploitability as an antiviral target for novel strategies of host-directed drug development.
CRIS-Team Scopus Importer:2024-10-04
Keywords: antiviral approach with CDK8-inhibitory small molecules; broad-spectrum antiviral CDK8 inhibitors; cyclin-dependent kinase 8 (CDK8); human cytomegalovirus (HCMV); human pathogenic herpesviruses; negative impact of CDK8 inhibitors; novel host-directed targeting strategies; regulation of viral replication; siRNA-mediated CDK8 knock-down; virus-supportive cellular protein kinases

Cyclin‐Dependent Kinases (CDKs) and the Human Cytomegalovirus‐Encoded CDK Ortholog pUL97 Represent Highly Attractive Targets for Synergistic Drug Combinations - Wild, Markus; Hahn, Friedrich; Brückner, Nadine; Schütz, Martin; Wangen, Christina; Wagner, Sabrina; Sommerer, Mona; Strobl, Stefan; Marschall, Manfred (International Journal of Molecular Sciences, 2022)
Human cytomegalovirus (HCMV) is a pathogenic human herpesvirus associated with serious, potentially life‐threatening symptoms in the immunocompromised or immunonaïve host. The limitations encountered by antiviral therapy options currently available include a narrow panel of accessible targets, the induction of viral drug resistance as well as severe drug dosage‐mediated side‐effects. Improved drug‐targeting strategies to resolve these issues are the focus of our investigations. In particular, pharmaceutical kinase inhibitors (PKIs), either directed to host kinases or directed to the viral protein kinase pUL97, have been considered to overcome these restrictions. Recently, we reported the identification of a synergistic combination of two PKIs directed to host cyclin‐dependent kinase 7 (CDK7) and viral CDK ortholog pUL97. Here, we substantiate these findings with the following results: (i) true drug synergy was exhibited by various chemical classes of PKI pairs directed to pUL97 and CDK7; (ii) no putative amplification of cytotoxicity by these drug combinations was observed; (iii) a reduction in drug dosage levels for synergistic combinations was defined on a quantitative basis and compared to monotreatments; (iv) the quantities of target proteins CDK7 and pUL97 expressed in HCMV‐infected cells were assessed by confocal imaging, indicating a strong down‐modulation of CDK7 levels as a result of synergistic drug treatment; (v) the functional importance of these target kinases, both binding to cyclin H, was illustrated by assessing HCMV replication under the viral genomic deletion of ORF‐UL97 or cellular cyclin knock‐out; (vi) new combinations of HCMV‐specific drug synergy were demonstrated for solely host‐directed treatments using PKIs against CDK2, CDK7, CDK8 and/or CDK9 and (vii) a triple PKI combination provided further support for the synergy approach. With these combined findings, this study highlights the potential of therapeutic drug combinations of approved, developmental and preclinical PKIs for expanding future options for anti‐HCMV therapy.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Antiviral drug; Antiviral drug synergism; Cyclin‐dependent kinase (CDK); Direct‐acting antiviral (DAA); Drug combinations; Host‐directed antiviral (HDA); Human cytomegalovirus; New synergistic drug‐target combinations; Pharmaceutical kinase inhibitor (PKI); Viral CDK pUL97 (vCDK)

Cyclins B1, T1, and H differ in their molecular mode of interaction with cytomegalovirus protein kinase pUL97 - Steingruber, Mirjam; Keller, Lena; Socher, Eileen; Ferre, Sabrina; Hesse, Anne-Marie; Coute, Yohann; Hahn, Friedrich; Buescher, Nicole; Plachter, Bodo; Sticht, Heinrich; Marschall, Manfred (Journal of Biological Chemistry, 2019)
Human cytomegalovirus (HCMV) is a common -herpesvirus causing life-long latent infections. HCMV replication interferes with cell cycle regulation in host cells because the HCMV-encoded cyclin-dependent kinase (CDK) ortholog pUL97 extensively phosphorylates the checkpoint regulator retinoblastoma protein. pUL97 also interacts with cyclins B1, T1, and H, and recent findings have strongly suggested that these interactions influence pUL97 substrate recognition. Interestingly, here we detected profound mechanistic differences among these pUL97– cyclin interactions. Our study revealed the following. (i) pUL97 interacts with cyclins B1 and H in a manner dependent on pUL97 activity and HCMV-specific cyclin modulation, respectively. (ii) The phosphorylated state of both proteins is an important determinant of the pUL97–cyclin B1 interaction. (iii) Activated phospho-Thr-315 cyclin H is up-regulated during HCMV replication. (iv) Thr-315 phosphorylation is independent of intracellular pUL97 or CDK7 activity. (v) pUL97-mediated in vitro phosphorylation is detectable for cyclin B1 but not H. (vi) Mutual transphosphorylation between pUL97 and CDK7 is not detectable, and an MS-based phosphosite analysis indicated that pUL97 might unexpectedly not be phosphorylated in its T-loop. (vii) The binary complexes pUL97– cyclin H and CDK7– cyclin H as well as the ternary complex pUL97– cyclin-H–CDK7 are detectable in an assembly-based CoIP approach. (viii) pUL97 self-interaction can be bridged by the transcriptional cyclins T1 or H but not by the classical cell cycle–regulating B1 cyclin. Combined, our findings unravel a number of cyclin type–specific differences in pUL97 interactions and suggest a multifaceted regulatory impact of cyclins on HCMV replication.
CRIS-Team Scopus Importer:2019-05-03

Cytomegalovirus cyclin-dependent kinase ortholog vCDK/pUL97 undergoes regulatory interaction with human cyclin H and CDK7 to codetermine viral replication efficiency - Schütz, Martin; Wangen, Christina; Sommerer, Mona; Kögler, Melanie; Eickhoff, Jan; Degenhart, Carsten; Klebl, Bert; Naing, Zin; Egilmezer, Ece; Hamilton, Stuart T.; Rawlinson, William D.; Sticht, Heinrich; et al. (Virus Research, 2023)
Human cytomegalovirus (HCMV) infection is shaped by a tightly regulated interplay between viral and cellular proteins. Distinct kinase activities, such as the viral cyclin-dependent kinase ortholog (vCDK) pUL97 and cellular CDK7 are both crucial for efficient viral replication. Previously, we reported that both kinases, vCDK/pUL97 and CDK7, interact with cyclin H, thereby achieving an enhanced level of kinase activity and overall functionality in viral replication. Here we provide a variety of novel results, as generated on a methodologically extended basis, and present a concept for the codetermination of viral replication efficiency through these kinase activities: (i) cyclin H expression, in various human cell types, is substantially upregulated by strains of HCMV including the clinically relevant HCMV Merlin; (ii) vCDK/pUL97 interacts with human cyclin H in both HCMV-infected and plasmid-transfected cell systems; (iii) a doxycycline-inducible shRNA-dependent knock-down (KD) of cyclin H significantly reduces pUL97 activity (qSox in vitro kinase assay); (iv) accordingly, pUL97 in vitro kinase activity is seen significantly increased upon addition of recombinant cyclin H; (v) as a point of specific importance, human CDK7 activity shows an increase by vCDK/pUL97-mediated trans-stimulation (whereas pUL97 is not stimulated by CDK7); (vi) phosphosite-specific antibodies indicate an upregulated CDK7 phosphorylation upon HCMV infection, as mediated through a pUL97-specific modulatory effect (i.e. shown by pUL97 inhibitor treatment or pUL97-deficient viral mutant); (vii) finally, an efficient KD of cyclin H in primary fibroblasts generally results in an impaired HCMV replication efficiency as measured on protein and genomic levels. These results show evidence for the codetermination of viral replication by vCDK/pUL97, cyclin H and CDK7, thus supporting the specific importance of cyclin H as a central regulatory factor, and suggesting novel targeting options for antiviral drugs.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Codetermination of viral replication; Cyclin H knock-down; Functional importance of cyclin H; Human cytomegalovirus; Modulation of vCDK/pUL97 activity in vitro; Options for antiviral drug targeting; pUL97-mediated CDK7 trans-stimulation; vCDK/pUL97–cyclin binding; Viral cyclin-dependent kinase (CDK) ortholog

Cytomegalovirus pUL50 is the multi-interacting determinant of the core nuclear egress complex (NEC) that recruits cellular accessory NEC components - Sonntag, Ellen; Hamilton, Stuart T.; Bahsi, Hanife; Wagner, Sabrina; Jonjic, Stipan; Rawlinson, William D.; Marschall, Manfred; Milbradt, Jens (Journal of General Virology, 2016)
Nuclear egress of herpesvirus capsids through the nuclear envelope is mediated by the multimeric nuclear egress complex (NEC). The human cytomegalovirus (HCMV) core NEC is defined by an interaction between the membrane-anchored pUL50 and its nuclear co-factor pUL53, tightly associated through heterodimeric corecruitment to the nuclear envelope. Cellular proteins, such as p32/gC1qR, emerin and protein kinase C (PKC), are recruited by direct interaction with pUL50 for the multimeric extension of the NEC. As a functionally important event, the recruitment of both viral and cellular protein kinases leads to site-specific lamin phosphorylation and nuclear lamina disassembly. In this study, interaction domains within pUL50 for its binding partners were defined by co-immunoprecipitation. The interaction domain for pUL53 is located within the pUL50 N-terminus (residues 10-169), interaction domains for p32/gC1qR (100-358) and PKC (100-280) overlap in the central part of pUL50, and the interaction domain for emerin is located in the C-terminus (265-397). Moreover, expression and formation of core NEC proteins at the nuclear rim were consistently detected in cells permissive for productive HCMV replication, including two trophoblast-cell lines. Importantly, regular nuclear-rim formation of the core NEC was blocked by inhibition of cyclin-dependent kinase (CDK) activity. In relation to the recently published crystal structure of the HCMV core NEC, our findings result in a refined view of NEC assembly. In particular, we suggest that CDKs may play an important regulatory role in NEC formation during HCMV replication.
EVALuna2:8320

Deeper Insight into the Six-Step Domino Reaction of Aldehydes with Malononitrile and Evaluation of Antiviral and Antimalarial Activities of the Obtained Bicyclic Products. - Bock, Christina; Gangajji, Parameshwarappa; Bönisch, Simon; Bauer, Walter; Hutterer, Corina; Leidenberger, Maria; Friedrich, Oliver; Marschall, Manfred; Kappes, Bärbel; Görling, Andreas; Tsogoeva, Svetlana (ChemistryOpen, 2017)
The straightforward and efficient synthesis of complex aza- and carbobicyclic compounds, which are of importance for medicinal chemistry, is a challenge for modern chemical methodology. An unprecedented metal-free six-step domino reaction of aldehydes with malononitrile was presented in our previous study to provide, in a single operation, these bicyclic nitrogen-containing molecules. Presented here is a deeper investigation of this atom-economical domino process by extending the scope of aldehydes, performing post-modifications of domino products, applying bifunctional organocatalysts and comprehensive NMR studies of selected domino products. The thermodynamic aspects of the overall reaction are also demonstrated using DFT methods in conjunction with a semi-empirical treatment of van der Waals interactions. Furthermore, biological studies of seven highly functionalized and artemisinin-containing domino products against human cytomegalovirus (HCMV) and Plasmodium falciparum 3D7 are presented. Remarkably, in vitro tests against HCMV revealed five domino products to be highly active compounds (EC50 0.071-1.8 μm), outperforming the clinical reference drug ganciclovir (EC50 2.6 μm). Against P. falciparum 3D7, three of the investigated artemisinin-derived domino products (EC50 0.72-1.8 nm) were more potent than the clinical drug chloroquine (EC50 9.1 nm).

Development of a PROTAC-based targeting strategy provides a mechanistically unique mode of anti-cytomegalovirus activity - Hahn, Friedrich; Hamilton, Stuart T.; Wangen, Christina; Wild, Markus; Kicuntod, Jintawee; Brückner, Nadine; Follett, Jasmine E.L.; Herrmann, Lars; Kheimar, Ahmed; Kaufer, Benedikt B.; Rawlinson, William D.; Tsogoeva, Svetlana; et al. (International Journal of Molecular Sciences, 2021)
Human cytomegalovirus (HCMV) is a major pathogenic herpesvirus that is prevalent worldwide and it is associated with a variety of clinical symptoms. Current antiviral therapy options do not fully satisfy the medical needs; thus, improved drug classes and drug-targeting strategies are required. In particular, host-directed antivirals, including pharmaceutical kinase inhibitors, might help improve the drug qualities. Here, we focused on utilizing PROteolysis TArgeting Chimeras (PROTACs), i.e., hetero-bifunctional molecules containing two elements, namely a target-binding molecule and a proteolysis-inducing element. Specifically, a PROTAC that was based on a cyclin-dependent kinase (CDK) inhibitor, i.e., CDK9-directed PROTAC THAL-SNS032, was analyzed and proved to possess strong anti-HCMV AD169-GFP activity, with values of EC50 of 0.030 µM and CC50 of 0.175 µM (SI of 5.8). Comparing the effect of THAL-SNS032 with its non-PROTAC counterpart SNS032, data indicated a 3.7-fold stronger anti-HCMV efficacy. This antiviral activity, as illustrated for further clinically relevant strains of human and murine CMVs, coincided with the mid-nanomolar concentration range necessary for a drug-induced degradation of the primary (CDK9) and secondary targets (CDK1, CDK2, CDK7). In addition, further antiviral activities were demonstrated, such as the inhibition of SARS-CoV-2 replication, whereas other investigated human viruses (i.e., varicella zoster virus, adenovirus type 2, and Zika virus) were found insensitive. Combined, the antiviral quality of this approach is seen in its (i) mechanistic uniqueness; (ii) future options of combinatorial drug treatment; (iii) potential broad-spectrum activity; and (iv) applicability in clinically relevant antiviral models. These novel data are discussed in light of the current achievements of anti-HCMV drug development.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Antiviral drugs; Direct-acting antivirals; Host-directed antivirals; Human cytomegalovirus; Human/animal pathogenic viruses; New drug qualities; PROTAC-based targeting strategy; PROteolysis TArgeting Chimeras

Differential properties of cytomegalovirus pUL97 kinase isoforms affect viral replication and maribavir susceptibility - Webel, Rike; Hakki, Morgan; Prichard, Mark N.; Rawlinson, William D.; Marschall, Manfred; Chou, Sunwen (Journal of Virology, 2014)
The human cytomegalovirus (HCMV)-encoded kinase pUL97 is required for efficient viral replication. Previous studies described two isoforms of pUL97, the full-length isoform (M1) and a smaller isoform likely resulting from translation initiation at codon 74 (M74). Here, we report the detection of a third pUL97 isoform during viral infection resulting from translation initiation at codon 157 (isoform M157). The consistent expression of isoform M157 as a minor component of pUL97 during infection with clinical and laboratory-adapted HCMV strains was suppressed when codon 157 was mutagenized. Viral mutants expressing specific isoforms were generated to compare their growth and drug susceptibility phenotypes, as well as pUL97 intracellular localization patterns and kinase activities. The exclusive expression of isoform M157 resulted in substantially reduced viral growth and resistance to the pUL97 inhibitor maribavir while retaining susceptibility to ganciclovir. Confocal imaging demonstrated reduced nuclear import of amino-terminal deletion isoforms compared to isoform M1. Isoform M157 showed reduced efficiency of various substrate protein interactions and autophosphorylation, whereas Rb phosphorylation was preserved. These results reveal differential properties of pUL97 isoforms that affect viral replication, with implications for the antiviral efficacy of maribavir.The HCMV UL97 kinase performs important functions in viral replication that are targeted by the antiviral drug maribavir. Here, we describe a naturally occurring short isoform of the kinase that when expressed by itself in a recombinant virus results in altered intracellular localization, impaired growth, and high-level resistance to maribavir compared to those of the predominant full-length counterpart. This is another factor to consider in explaining why maribavir appears to have variable antiviral activity in cell culture and in vivo.
EVALuna2:8230

Differential upregulation of host cell protein kinases by the replication of α-, β- and γ-herpesviruses provides a signature of virus-specific signalling - Marschall, Manfred; Strojan, Hanife; Kiener, Richard; Wangen, Christina; Sonntag, Eric; Müller, Regina; Zeitträger, Isabel; Wagner, Sabrina; Stamminger, Thomas; Milbradt, Jens; Behrends, Uta; Körber, Nina; et al. (Journal of General Virology, 2020)
Infections with human herpesviruses share several molecular characteristics, but the diversified medical outcomes are distinct to viral subfamilies and species. Notably, both clinical and molecular correlates of infection are a challenging field and distinct patterns of virus-host interaction have rarely been defined; this study therefore focuses on the search for virus-specific molecular indicators. As previous studies have demonstrated the impact of herpesvirus infections on changes in host signalling pathways, we illustrate virus-modulated expression levels of individual cellular protein kinases. Current data reveal (i) α-, β- and γ-herpesvirus-specific patterns of kinase modulation as well as (ii) differential levels of up-/downregulated kinase expression and phosphorylation, which collectively suggest (iii) defined signalling patterns specific for the various viruses (VSS) that may prove useful for defining molecular indicators. Combined, the study confirms the correlation between herpesviral replication and modulation of signalling kinases, possibly exploitable for the in vitro characterization of viral infections.
CRIS-Team Scopus Importer:2020-04-10
Keywords: differential upregulation of cellular kinases; herpesviral replication; modulation of the host kinome; primary human fibroblasts; signature of virus-specific signalling

Dynamic regulatory interaction between cytomegalovirus major tegument protein pp65 and protein kinase pUL97 in intracellular compartments, dense bodies and virions - König, Patrick; Buescher, Nicoie; Steingruber, Mirjam; Socher, Eileen; Sticht, Heinrich; Tenzer, Stefan; Plachter, Bodo; Marschall, Manfred (Journal of General Virology, 2017)
Human cytomegalovirus (HCMV) is a ubiquitous pathogen of considerable clinical importance. Understanding the processes that are important for viral replication is essential for the development of therapeutic strategies against HCMV infection. The HCMV-encoded protein kinase pUL97 is an important multifunctional regulator of viral replication. Several viral and cellular proteins are phosphorylated by pUL97. The phosphoprotein pp65 is one important substrate of pUL97. It is the most abundant tegument protein of HCMV virions, mediating the upload of other virion constituents and contributing to particle integrity. Further to that, it interferes with host innate immune defences, thereby enabling efficient viral replication. By applying different approaches, we characterized the pp65-pUL97 interaction in various compartments. Specifically, the pUL97 interaction domain of pp65 was defined (282-415). A putative cyclin bridge that enhances pUL97-pp65 interaction was identified. The impact of pUL97 mutation on virion and dense body morphogenesis was addressed using pUL97 mutant viruses. Alterations in the proteome of viral particles were seen, especially with mutant viruses expressing cytoplasmic variants of pUL97. On the basis of these data we postulate a so far poorly recognized functional relationship between pp65 and pUL97, and present a refined model of pp65-pUL97 interaction.
EVALuna2:33718

Establishment of a Luciferase-Based Reporter System to Study Aspects of Human Cytomegalovirus Infection, Replication Characteristics, and Antiviral Drug Efficacy - Tillmanns, Julia; Kicuntod, Jintawee; Ehring, Antonia; Elbasani, Endrit; Borst, Eva Maria; Obergfäll, Debora; Müller, Regina; Hahn, Friedrich; Marschall, Manfred (Pathogens, 2024)
Human cytomegalovirus (HCMV) represents a highly medically important pathogen which has constantly been the subject of both molecular and clinical investigations. HCMV infections, especially those in high-risk patients, still raise many unanswered questions, so current investigations are focused on viral pathogenesis, vaccine development, and options for antiviral drug targeting. To this end, the use of suitable viral strains as well as recombinant reporter constructs in cultured cells and model systems has specific significance. We previously reported on the application of various herpesviruses that express green, red, or related fluorescent proteins, especially in the fields of virus–host interaction and antiviral research. Here, we characterized a recombinant version of the clinically relevant and cell type-adaptable HCMV strain TB40, which expresses firefly luciferase as a quantitative reporter of viral replication (TB40-FLuc). The data provide evidence for five main conclusions. First, HCMV TB40-FLuc is employable in multiple settings in primary human cells. Second, viral reporter signals are easily quantifiable, even at early time points within viral replication. Third, the FLuc reporter reflects the kinetics of viral intracellular replication, cascade-like viral IE-E-L protein production, and progeny release. Fourth, as relates to specific applications of the TB40-FLuc system, we demonstrated the reliability of quantitative antiviral compound determination in multi-well formats and its independence from fluorescence-based measurements in the case of autofluorescent inhibitors. Finally, we illustrated increased reporter sensitivity in comparison to other recombinant HCMVs. In essence, recombinant HCMV TB40-FLuc combines several molecular properties that are considered beneficial in studies on viral host tropism, replication efficiency, and antiviral drug assessment.
CRIS-Team Scopus Importer:2024-09-06
Keywords: advantages of the reporter system; antiviral drug development; firefly luciferase reporter (FLuc); future applications in molecular HCMV analysis; human cytomegalovirus (HCMV); infection of primary human cultured cells; medically important viral pathogens; recombinant HCMV TB40-FLuc; viral replication characteristics and efficiency

Exploring the Human Cytomegalovirus Core Nuclear Egress Complex as a Novel Antiviral Target: A New Type of Small Molecule Inhibitors - Alkhashrom, Sewar; Kicuntod, Jintawee; Häge, Sigrun; Schweininger, Johannes; Muller, Yves; Lischka, Peter; Marschall, Manfred; Eichler, Jutta (Viruses, 2021)
Nuclear egress is an essential process in the replication of human cytomegalovirus (HCMV), as it enables the migration of newly formed viral capsids from the nucleus into the cytoplasm. Inhibition of the HCMV core nuclear egress complex (core NEC), composed of viral proteins pUL50 and pUL53, has been proposed as a potential new target for the treatment of HCMV infection and disease. Here, we present a new type of small molecule inhibitors of HCMV core NEC formation, which inhibit the pUL50-pUL53 interaction at nanomolar concentrations. These inhibitors, i.e., verteporfin and merbromin, were identified through the screening of the Prestwick Chemical Library® of approved drug compounds. The inhibitory effect of merbromin is both compound- and target-specific, as no inhibition was seen for other mercury-organic compounds. Furthermore, merbromin does not inhibit an unrelated protein-protein interaction either. More importantly, merbromin was found to inhibit HCMV infection of cells in three different assays, as well as to disrupt HCMV NEC nuclear rim formation. Thus, while not being an ideal drug candidate by itself, merbromin may serve as a blueprint for small molecules with high HCMV core NEC inhibitory potential, as candidates for novel anti-herpesviral drugs.
CRIS-Team Scopus Importer:2021-04-16
Keywords: antiviral activity; core NEC inhibitor; human cytomegalovirus; nuclear egress complex (NEC); small molecule inhibitor

Facile access to potent antiviral quinazoline heterocycles with fluorescence properties via merging metal-free domino reactions - Held, Felix; Guryev, Anton; Fröhlich, Tony; Hampel, Frank; Kahnt, Axel; Hutterer, Corina; Steingruber, Mirjam; Bahsi, Hanife; Von Bojnicic-Kninski, Clemens; Mattes, Daniela S.; Foertsch, Tobias C.; Nesterov-Mueller, Alexander; et al. (Nature Communications, 2017)
Most of the known approved drugs comprise functionalized heterocyclic compounds as subunits. Among them, non-fluorescent quinazolines with four different substitution patterns are found in a variety of clinically used pharmaceuticals, while 4,5,7,8-substituted quinazolines and those displaying their own specific fluorescence, favourable for cellular uptake visualization, have not been described so far. Here we report the development of a one-pot synthetic strategy to access these 4,5,7,8-substituted quinazolines, which are fluorescent and feature strong antiviral properties (EC50down to 0.6±0.1 μM) against human cytomegalovirus (HCMV). Merging multistep domino processes in one-pot under fully metal-free conditions leads to sustainable, maximum efficient and high-yielding organic synthesis. Furthermore, generation of artesunic acid-quinazoline hybrids and their application against HCMV (EC50down to 0.1±0.0 μM) is demonstrated. Fluorescence of new antiviral hybrids and quinazolines has potential applications in molecular imaging in drug development and mechanistic studies, avoiding requirement of linkage to external fluorescent markers.
EVALuna2:33762

Facile Synthesis of New Antiviral Fluoro-Quinazolines Enabled by Merging Domino Reactions - Kohlbauer, Sascha; Xia, Honglin; Grau, Benedikt; Wangen, Christina; Hahn, Friedrich; Nenajdenko, Valentine G.; Marschall, Manfred; Tsogoeva, Svetlana (Synthesis (Germany), 2025)
Quinazolines, particularly fluoro-quinazolines, represent important structural motifs in bioactive molecules and pharmaceuticals. Despite several known synthetic routes, the efficient synthesis of fluorine-containing quinazolines remains a challenge. Herein, the straightforward and sustainable synthesis of fluorine-substituted quinazolines using domino sequences is reported. The obtained novel fluoro-quinazoline compounds exhibit significant in vitro activity against human cytomegalovirus (HCMV), expanding the library of potential antiviral drug compounds. Our finding outlays the synthetic toolkit for fluoro-quinazolines and introduces new agents for HCMV therapy.
CRIS-Team Scopus Importer:2024-11-29
Keywords: antiviral agents; domino reaction; fluoro-quinazolines; heterocycles; one-pot reaction

Functional Relevance of the Interaction between Human Cyclins and the Cytomegalovirus-Encoded CDK-Like Protein Kinase pUL97 - Schütz, Martin; Steingruber, Mirjam; Socher, Eileen; Müller, Regina; Wagner, Sabrina; Kögel, Merle; Sticht, Heinrich; Marschall, Manfred (Viruses, 2021)
The replication of human cytomegalovirus (HCMV) is characterized by a complex network of virus–host interaction. This involves the regulatory viral protein kinase pUL97, which represents a viral cyclin-dependent kinase ortholog (vCDK) combining typical structural and functional features of host CDKs. Notably, pUL97 interacts with the three human cyclin types T1, H and B1, whereby the binding region of cyclin T1 and the region conferring oligomerization of pUL97 were both assigned to amino acids 231–280. Here, we addressed the question of whether recombinant HCMVs harboring deletions in this region were impaired in cyclin interaction, kinase functionality or viral replication. To this end, recombinant HCMVs were generated by traceless BACmid mutagenesis and were phenotypically characterized using a methodological platform based on qPCR, coimmunoprecipitation, in vitro kinase assay (IVKA), Phos-tag Western blot and confocal imaging analysis. Combined data illustrate the following: (i) infection kinetics of all three recombinant HCMVs, i.e., ORF-UL97 ∆231–255, ∆256–280 and ∆231–280, showed impaired replication efficiency compared to the wild type, amongst which the largest deletion exhibited the most pronounced defect; (ii) specifically, this mutant ∆231–280 showed a loss of interaction with cyclin T1, as demonstrated by CoIP and confocal imaging; (iii) IVKA and Phos-tag analyses revealed strongly affected kinase activity for ∆231–280, with strong impairment of both autophosphorylation and substrate phosphorylation, but less pronounced impairments for ∆231–255 and ∆256–280; and (iv) a bioinformatic assessment of the pUL97–cyclin T1 complex led to the refinement of our current binding model. Thus, the results provide initial evidence for the functional importance of the pUL97–cyclin interaction concerning kinase activity and viral replication fitness.<br
Keywords: human cytomegalovirus; virus-encoded kinase pUL97; viral CDK ortholog; interaction with human cyclin T1; replication-impaired viral mutants; defects in pUL97 activities; pUL97–cyclin functional importance

‘Getting Better’—Is It a Feasible Strategy of Broad Pan-Antiherpesviral Drug Targeting by Using the Nuclear Egress-Directed Mechanism? - Tillmanns, Julia; Kicuntod, Jintawee; Lösing, Josephine; Marschall, Manfred (International Journal of Molecular Sciences, 2024)
The herpesviral nuclear egress represents an essential step of viral replication efficiency in host cells, as it defines the nucleocytoplasmic release of viral capsids. Due to the size limitation of the nuclear pores, viral nuclear capsids are unable to traverse the nuclear envelope without a destabilization of this natural host-specific barrier. To this end, herpesviruses evolved the regulatory nuclear egress complex (NEC), composed of a heterodimer unit of two conserved viral NEC proteins (core NEC) and a large-size extension of this complex including various viral and cellular NEC-associated proteins (multicomponent NEC). Notably, the NEC harbors the pronounced ability to oligomerize (core NEC hexamers and lattices), to multimerize into higher-order complexes, and, ultimately, to closely interact with the migrating nuclear capsids. Moreover, most, if not all, of these NEC proteins comprise regulatory modifications by phosphorylation, so that the responsible kinases, and additional enzymatic activities, are part of the multicomponent NEC. This sophisticated basis of NEC-specific structural and functional interactions offers a variety of different modes of antiviral interference by pharmacological or nonconventional inhibitors. Since the multifaceted combination of NEC activities represents a highly conserved key regulatory stage of herpesviral replication, it may provide a unique opportunity towards a broad, pan-antiherpesviral mechanism of drug targeting. This review presents an update on chances, challenges, and current achievements in the development of NEC-directed antiherpesviral strategies.
CRIS-Team Scopus Importer:2024-03-22
Keywords: core and multicomponent NEC extensions; cytomegalovirus (HCMV); essential steps of viral replication; human pathogenic herpesviruses; NEC-directed mode of action; novel antiviral drug targeting; nuclear egress complex (NEC); strategies of antiviral drug development; viral nucleocytoplasmic capsid egress

Highly Conserved Interaction Profiles between Clinically Relevant Mutants of the Cytomegalovirus CDK-like Kinase pUL97 and Human Cyclins: Functional Significance of Cyclin H - Schütz, Martin; Müller, Regina; Socher, Eileen; Wangen, Christina; Full, Florian; Wyler, Emanuel; Wong, Diana D.; Scherer, Myriam; Stamminger, Thomas; Chou, Sunwen; Rawlinson, William D.; Hamilton, Stuart T.; et al. (International Journal of Molecular Sciences, 2022)
The complex host interaction network of human cytomegalovirus (HCMV) involves the regulatory protein kinase pUL97, which represents a viral cyclin-dependent kinase (CDK) ortholog. pUL97 interacts with the three human cyclin types T1, H, and B1, whereby the binding region of cyclin T1 and the pUL97 oligomerization region were both assigned to amino acids 231-280. We further addressed the question of whether HCMVs harboring mutations in ORF-UL97, i.e., short deletions or resistance-conferring point mutations, are affected in the interaction with human cyclins and viral replication. To this end, clinically relevant UL97 drug-resistance-conferring mutants were analyzed by whole-genome sequencing and used for genetic marker transfer experiments. The recombinant HCMVs indicated conservation of pUL97–cyclin interaction, since all viral UL97 point mutants continued to interact with the analyzed cyclin types and exerted wild-type-like replication fitness. In comparison, recombinant HCMVs UL97 Δ231-280 and also the smaler deletion Δ236-275, but not Δ241-270, lost interaction with cyclins T1 and H, showed impaired replication efficiency, and also exhibited reduced kinase activity. Moreover, a cellular knock-out of cyclins B1 or T1 did not alter HCMV replication phenotypes or pUL97 kinase activity, possibly indicating alternative, compensatory pUL97–cyclin interactions. In contrast, however, cyclin H knock-out, similar to virus deletion mutants in the pUL97–cyclin H binding region, exhibited strong defective phenotypes of HCMV replication, as supported by reduced pUL97 kinase activity in a cyclin H-dependent coexpression setting. Thus, cyclin H proved to be a very relevant determinant of pUL97 kinase activity and viral replication efficiency. As a conclusion, the results provide evidence for the functional importance of pUL97–cyclin interaction. High selective pressure on the formation of pUL97–cyclin complexes was identified by the use of clinically relevant mutants<br

Highly potent artemisinin-derived dimers and trimers: Synthesis and evaluation of their antimalarial, antileukemia and antiviral activities. - Reiter, Christoph; Fröhlich, Tony; Gruber, Lisa; Hutterer, Corina; Marschall, Manfred; Voigtländer, Cornelia; Friedrich, Oliver; Kappes, Bärbel; Efferth, Thomas; Tsogoeva, Svetlana (Bioorganic & medicinal chemistry, 2015)
New pharmaceutically active compounds can be obtained by modification of existing drugs to access more effective agents in the wake of drug resistance amongst others. To achieve this goal the concept of hybridization was established during the last decade. We employed this concept by coupling two artemisinin-derived precursors to obtain dimers or trimers with increased in vitro activity against Plasmodiumfalciparum 3D7 strain, leukemia cells (CCRF-CEM and multidrug-resistant subline CEM/ADR5000) and human cytomegalovirus (HCMV). Dimer 4 (IC50 of 2.6nM) possess superior antimalarial activity compared with its parent compound artesunic acid(3) (IC50 of 9.0nM). Dimer5 and trimers6 and 7 display superior potency against both leukemia cell lines (IC50 up to 0.002μM for CCRF-CEM and IC50 up to 0.20μM for CEM/ADR5000) and are even more active than clinically used doxorubicin (IC50 1.61μM for CEM/ADR5000). With respect to anti-HCMV activity, trimer6 is the most efficient hybrid (IC50 0.04μM) outperforming ganciclovir (IC50 2.6μM), dihydroartemisinin(IC50 >10μM) and artesunic acid (IC50 3.8μM).
Keywords: Artemisinin-derived hybrids; Artemisinin-derived dimers; Artemisinin-derived trimers; Antimalarial activity; Anticancer activity; Antiviral activity

High-resolution crystal structures of two prototypical β- And γ-herpesviral nuclear egress complexes unravel the determinants of subfamily specificity - Muller, Yves; Häge, Sigrun; Alkhashrom, Sewar; Höllriegl, Tobias; Weigert, Sebastian; Dolles, Simon; Hof, Kerstin; Walzer, Sascha; Egerer-Sieber, Claudia; Conrad, Marcus; Holst, Stephanie; Lösing, Josephine; et al. (Journal of Biological Chemistry, 2020)
Herpesviruses uniquely express two essential nuclear egress-regulating proteins forming a heterodimeric basic structure of the nuclear egress complex (core NEC). These core NECs serve as a hexameric lattice-structured platform for capsid docking and recruit viral and cellular NEC-associated factors that jointly exert nuclear lamina- and membrane-rearranging functions (multicomponent NEC). Here, we report the X-ray structures of β- and γ-herpesvirus core NECs obtained through an innovative recombinant expression strategy based on NEC-hook::NEC-groove protein fusion constructs. This approach yielded the first structure of γ-herpesviral core NEC, namely the 1.56 Å structure of Epstein-Barr virus (EBV) BFRF1-BFLF2, as well as an increased resolution 1.48 Å structure of human cytomegalovirus (HCMV) pUL50-pUL53. Detailed analysis of these structures revealed that the prominent hook segment is absolutely required for core NEC formation and contributes approximately 80% of the interaction surface of the globular domains of NEC proteins. Moreover, using HCMV::EBV hook domain swap constructs, computational prediction of the roles of individual hook residues for binding, and quantitative binding assays with synthetic peptides presenting the HCMV- and EBV-specific NEC hook sequences, we characterized the unique hook-into-groove NEC interaction at various levels. Although the overall physicochemical characteristics of the protein interfaces differ considerably in these β- and γ-herpesvirus NECs, the binding free energy contributions of residues displayed from identical positions are similar. In summary, the results of our study reveal critical details of the molecular mechanism of herpesviral NEC interactions and highlight their potential as an antiviral drug target.
CRIS-Team Scopus Importer:2020-03-17

Human cytomegaloviral multifunctional protein kinase pUL97 impairs zebrafish embryonic development and increases mortality - Cazorla-Vázquez, Salvador; Steingruber, Mirjam; Marschall, Manfred; Engel, Felix (Scientific Reports, 2019)
Cytomegalovirus is a worldwide-distributed human pathogen, which is the leading cause of congenital virus infection, affecting 0.5 to 2% of live births. To date, it is largely unclear which molecular mechanisms underlie the symptomatic outcomes. This is mainly due to species specificity and limited homology among cytomegalovirus genomes. As it is not possible to infect model organisms with human cytomegalovirus, the aim of this study was to develop a heterologous system allowing in the future the elucidation of the pathological role of individual viral proteins. As a model organism the zebrafish has been chosen due to its ease of manipulation and characterization as well as its large offspring. As cytomegalovirus model protein, pUL97 was characterized because it is multiply involved in virus-host interaction. Here, we show in zebrafish embryos, that (i) pUL97 can be expressed in zebrafish, (ii) increasing pUL97 expression levels quantitatively correlate with both minor and major pathological defects, (iii) pUL97 expression impairs cell cycle progression and induces cell death, (iv) active pUL97, but not an inactive mutant, induces excess mortality, and (v) co-administration of a pUL97 inhibitor reduces embryonic pathology. Collectively, these data indicate the suitability of zebrafish to elucidate the pathological role of human cytomegaloviral proteins.
CRIS-Team Scopus Importer:2019-05-24

Human cytomegalovirus (CMV) dysregulates neurodevelopmental pathways in cerebral organoids - Egilmezer, Ece; Hamilton, Stuart T.; Foster, Charles S.P.; Marschall, Manfred; Rawlinson, William D. (Communications Biology, 2024)
Human cytomegalovirus (CMV) infection is the leading non-genetic aetiology of congenital malformation in developed countries, causing significant fetal neurological injury. This study investigated potential CMV pathogenetic mechanisms of fetal neural malformation using in vitro human cerebral organoids. Cerebral organoids were permissive to CMV replication, and infection dysregulated cellular pluripotency and differentiation pathways. Aberrant expression of dual-specificity tyrosine phosphorylation-regulated kinases (DYRK), sonic hedgehog (SHH), pluripotency, neurodegeneration, axon guidance, hippo signalling and dopaminergic synapse pathways were observed in CMV-infected organoids using immunofluorescence and RNA-sequencing. Infection with CMV resulted in dysregulation of 236 Autism Spectrum Disorder (ASD)-related genes (p = 1.57E-05) and pathways. This notable observation suggests potential links between congenital CMV infection and ASD. Using DisGeNET databases, 103 diseases related to neural malformation or mental disorders were enriched in CMV-infected organoids. Cytomegalovirus infection-related dysregulation of key cerebral cellular pathways potentially provides important, modifiable pathogenetic mechanisms for congenital CMV-induced neural malformation and ASD.
CRIS-Team Scopus Importer:2024-03-29

Human Cytomegalovirus Dysregulates Cellular Dual-Specificity Tyrosine Phosphorylation-Regulated Kinases and Sonic Hedgehog Pathway Proteins in Neural Astrocyte and Placental Models - Egilmezer, Ece; Hamilton, Stuart T.; Lauw, Glen; Follett, Jasmine; Sonntag, Eric; Schütz, Martin; Marschall, Manfred; Rawlinson, William D. (Viruses, 2024)
Human cytomegalovirus (CMV) infection is the leading non-genetic cause of congenital malformation in developed countries, causing significant fetal injury, and in some cases fetal death. The pathogenetic mechanisms through which this host-specific virus infects then damages both the placenta and the fetal brain are currently ill-defined. We investigated the CMV modulation of key signaling pathway proteins for these organs including dual-specificity tyrosine phosphorylation-regulated kinases (DYRK) and Sonic Hedgehog (SHH) pathway proteins using human first trimester placental trophoblast (TEV-1) cells, primary human astrocyte (NHA) brain cells, and CMV-infected human placental tissue. Immunofluorescence demonstrated the accumulation and re-localization of SHH proteins in CMV-infected TEV-1 cells with Gli2, Ulk3, and Shh re-localizing to the CMV cytoplasmic virion assembly complex (VAC). In CMV-infected NHA cells, DYRK1A re-localized to the VAC and DYRK1B re-localized to the CMV nuclear replication compartments, and the SHH proteins re-localized with a similar pattern as was observed in TEV-1 cells. Western blot analysis in CMV-infected TEV-1 cells showed the upregulated expression of Rb, Ulk3, and Shh, but not Gli2. In CMV-infected NHA cells, there was an upregulation of DYRK1A, DYRK1B, Gli2, Rb, Ulk3, and Shh. These in vitro monoculture findings are consistent with patterns of protein upregulation and re-localization observed in naturally infected placental tissue and CMV-infected ex vivo placental explant histocultures. This study reveals CMV-induced changes in proteins critical for fetal development, and identifies new potential targets for CMV therapeutic development.
CRIS-Team Scopus Importer:2024-07-12
Keywords: astrocytes; cytomegalovirus; developmental pathways; pathogenesis; placenta

Human Cytomegalovirus Nuclear Capsids Associate with the Core Nuclear Egress Complex and the Viral Protein Kinase pUL97 - Milbradt, Jens; Sonntag, Eric; Wagner, Sabrina; Strojan, Hanife; Wangen, Christina; Rovis, Tihana Lenac; Lisnic, Berislav; Jonjic, Stipan; Sticht, Heinrich; Britt, William J.; Schlötzer-Schrehardt, Ursula; Marschall, Manfred (Viruses, 2018)
The nuclear phase of herpesvirus replication is regulated through the formation of regulatory multi-component protein complexes. Viral genomic replication is followed by nuclear capsid assembly, DNA encapsidation and nuclear egress. The latter has been studied intensely pointing to the formation of a viral core nuclear egress complex (NEC) that recruits a multimeric assembly of viral and cellular factors for the reorganization of the nuclear envelope. To date, the mechanism of the association of human cytomegalovirus (HCMV) capsids with the NEC, which in turn initiates the specific steps of nuclear capsid budding, remains undefined. Here, we provide electron microscopy-based data demonstrating the association of both nuclear capsids and NEC proteins at nuclear lamina budding sites. Specifically, immunogold labelling of the core NEC constituent pUL53 and NEC-associated viral kinase pUL97 suggested an intranuclear NEC-capsid interaction. Staining patterns with phospho-specific lamin A/C antibodies are compatible with earlier postulates of targeted capsid egress at lamina-depleted areas. Important data were provided by co-immunoprecipitation and in vitro kinase analyses using lysates from HCMV-infected cells, nuclear fractions, or infectious virions. Data strongly suggest that nuclear capsids interact with pUL53 and pUL97. Combined, the findings support a refined concept of HCMV nuclear trafficking and NEC-capsid interaction.
EVALuna2:33716

Human Cytomegalovirus Nuclear Egress Proteins Ectopically Expressed in the Heterologous Environment of Plant Cells are Strictly Targeted to the Nuclear Envelope - Lamm, Christian; Link, Katrin; Wagner, Sabrina; Milbradt, Jens; Marschall, Manfred; Sonnewald, Uwe (Viruses, 2016)
In all eukaryotic cells, the nucleus forms a prominent cellular compartment containing the cell's nuclear genome. Although structurally similar, animal and plant nuclei differ substantially in details of their architecture. One example is the nuclear lamina, a layer of tightly interconnected filament proteins (lamins) underlying the nuclear envelope of metazoans. So far no orthologous lamin genes could be detected in plant genomes and putative lamin-like proteins are only poorly described in plants. To probe for potentially conserved features of metazoan and plant nuclear envelopes, we ectopically expressed the core nuclear egress proteins of human cytomegalovirus pUL50 and pUL53 in plant cells. pUL50 localizes to the inner envelope of metazoan nuclei and recruits the nuclear localized pUL53 to it, forming heterodimers. Upon expression in plant cells, a very similar localization pattern of both proteins could be determined. Notably, pUL50 is specifically targeted to the plant nuclear envelope in a rim-like fashion, a location to which coexpressed pUL53 becomes strictly corecruited from its initial nucleoplasmic distribution. Using pUL50 as bait in a yeast two-hybrid screening, the cytoplasmic re-initiation supporting protein RISP could be identified. Interaction of pUL50 and RISP could be confirmed by coexpression and coimmunoprecipitation in mammalian cells and by confocal laser scanning microscopy in plant cells, demonstrating partial pUL50-RISP colocalization in areas of the nuclear rim and other intracellular compartments. Thus, our study provides strong evidence for conserved structural features of plant and metazoan nuclear envelops and identifies RISP as a potential pUL50-interacting plant protein.
Keywords: pUL53; plant cells; nuclear envelope; pUL50; re-initiation supporting protein RISP; human cytomegalovirus

Human cytomegalovirus replication is strictly inhibited by siRNAs targeting UL54, UL97 or UL122/123 gene transcripts - Hamilton, Stuart T.; Milbradt, Jens; Marschall, Manfred; Rawlinson, William D. (PLoS ONE, 2014)
Human cytomegalovirus (HCMV) causes severe sequelae in immunocompromised hosts. Current antiviral therapies have serious adverse effects, with treatment in many clinical settings problematic, making new therapeutic approaches necessary. We examined the in vitro efficacy of small interfering RNAs (siRNAs) targeting the HCMV gene transcripts UL54 (DNA polymerase), UL97 (protein kinase) and UL122/123 (immediate-early proteins) as inhibitors of viral protein expression and virus replication in cell cultures. Two siRNAs for each HCMV target (designated A and B) were assessed for inhibition efficacy using western blot and standard plaque assays. Continuous human embryonic kidney 293T cells were treated with HCMV or non-specific scrambled (siSc) siRNA followed by transfection with plasmids expressing the target transcripts. Human MRC-5 fibroblasts were HCMV-siRNA or siSc treated, infected with HCMV strain AD169 (1 pfu/cell) and HCMV immediate-early (IE1p72 and IE2p86), early (pp65), early-late (pUL97) and true late (MCP) protein and virus progeny production measured during a single round of replication. Concordant results showed siUL54B, siUL97A and siUL122B displayed the most potent inhibitory effects with a reduction of 92.7%, 99.6% and 93.7% in plasmid protein expression, 65.9%, 58.1% and 64.8% in total HCMV protein expression and 97.2%, 96.2% and 94.3% (p<0.0001) in viral progeny production respectively. Analysing the siRNA inhibitory effects during multiple rounds of HCMV replication at a multiplicity of infection of 0.001 pfu/cell, siUL54B, siUL97A and siUL122B treatment resulted in a reduction of 80.0%, 59.6% and 84.5% in total HCMV protein expression, 52.9%, 49.2% and 58.3% in number of cells infected and 98.5%, 91.4% and 99.1% (p<0.0001) in viral progeny production at 7 dpi respectively. These results suggest potential in vivo siRNA therapies targeting the HCMV gene transcripts UL54, UL97 and UL122/123 would be highly effective, however, the antiviral efficacy of siRNAs targeting UL97 may be more highly dependent on viral load and methods of administration.
EVALuna2:8236

Human cytomegalovirus utilises cellular dual-specificity tyrosine phosphorylation-regulated kinases during placental replication - Hamilton, Stuart T.; Hutterer, Corina; Egilmezer, Ece; Steingruber, Mirjam; Milbradt, Jens; Marschall, Manfred; Rawlinson, William D. (Placenta, 2018)
Introduction: Congenital cytomegalovirus (HCMV) infection may cause significant fetal malformation and in severe cases fetal and neonatal death. Fetal injury may be caused indirectly by the placental response to infection. Dual-specificity tyrosine phosphorylation-regulated kinases (DYRKs) have recently been identified as critical kinases for HCMV replication. In this study we provide first evidence that DYRK1A and DYRK1B are utilised during HCMV placental replication. Methods: DYRK expression was investigated in AD169-and Merlin-infected TEV-1 trophoblast cells, ex vivo placental explants and naturally infected clinical placentae by immunofluorescence, western blot, co-immunoprecipitation and RT-qPCR. Results: HCMV-infected placental cells showed accumulation and re-localisation of DYRK1A and DYRK1B protein to areas of cytoplasmic virion assembly complexes and nuclear viral replication compartments, respectively. This accumulation was a result of upregulated DYRK1A/B protein expression with HCMV inducing up to a 5.3fold increase in DYRK1A and up to a 4.7-fold increase in DYRK1B protein, relative to mock-infected TEV-1 cells (p < 0.0001). Increased DYRK protein expression was correlated with DYRK1A/B mRNA upregulation, with HCMV-infected cells showing up to a 3.7-fold increase and 2.9-fold increase in DYRK1A and DYRK1B mRNA levels respectively (p < 0.05). Protein-protein interactions were detected between DYRK1A/1B complexes and HCMV immediate early IE2p86, early pp65 and pUL44 and late pp150 proteins. Treatment of HCMV-infected TEV-1 cells and placental explants with DYRK inhibitors significantly inhibited HCMV replication (p < 0.05) indicating these cellular kinases are required during HCMV placental replication. Conclusion: HCMV modulates cellular DYRKs during placental replication which may have implications for congenital HCMV pathogenesis and represent promising antiviral targets.
EVALuna2:35259

IMU-838, a Developmental DHODH Inhibitor in Phase II for Autoimmune Disease, Shows Anti-SARS-CoV-2 and Broad-Spectrum Antiviral Efficacy In Vitro - Hahn, Friedrich; Wangen, Christina; Häge, Sigrun; Peter, Antonia Sophia; Dobler, Gerhard; Hurst, Brett; Julander, Justin; Fuchs, Jonas; Ruzsics, Zsolt; Überla, Klaus; Jäck, Hans-Martin; Ptak, Roger; et al. (Viruses, 2020)
The ongoing pandemic spread of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) demands skillful strategies for novel drug development, drug repurposing and cotreatments, in particular focusing on existing candidates of host-directed antivirals (HDAs). The developmental drug IMU-838, currently being investigated in a phase 2b trial in patients suffering from autoimmune diseases, represents an inhibitor of human dihydroorotate dehydrogenase (DHODH) with a recently proven antiviral activity in vitro and in vivo. Here, we established an analysis system for assessing the antiviral potency of IMU-838 and DHODH-directed back-up drugs in cultured cell-based infection models. By the use of SARS-CoV-2-specific immunofluorescence, Western blot, in-cell ELISA, viral yield reduction and RT-qPCR methods, we demonstrated the following: (i) IMU-838 and back-ups show anti-SARS-CoV-2 activity at several levels of viral replication, i.e., protein production, double-strand RNA synthesis, and release of infectious virus; (ii) antiviral efficacy in Vero cells was demonstrated in a micromolar range (IMU-838 half-maximal effective concentration, EC50, of 7.6 ± 5.8 µM); (iii) anti-SARS-CoV-2 activity was distinct from cytotoxic effects (half-cytotoxic concentration, CC50, >100 µM); (iv) the drug in vitro potency was confirmed using several Vero lineages and human cells; (v) combination with remdesivir showed enhanced anti-SARS-CoV-2 activity; (vi) vidofludimus, the active determinant of IMU-838, exerted a broad-spectrum activity against a selection of major human pathogenic viruses. These findings strongly suggest that developmental DHODH inhibitors represent promising candidates for use as anti-SARS-CoV-2 therapeutics.
CRIS-Team Scopus Importer:2020-12-25
Keywords: antiviral therapy; dihydroorotate dehydrogenase (DHODH) inhibitors; host-directed antivirals (HDAs); IMU-838; SARS-CoV-2; vidofludimus

IMU-838, a small molecule DHODH inhibitor in phase II clinical trial for multiple sclerosis, shows potent Anti-EBV activity in cell-culture-based systems: Potential additional benefits in multiple sclerosis treatment - Marschall, Manfred; Peelen, E.; Müller, Regina; Wangen, C.; Wagner, Sören; Muehler, A.; Groeppel, M.; Vitt, D.; Kohlhof, H.; Hahn, Friedrich (MULTIPLE SCLEROSIS JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-03

Inhibitors of dual-specificity tyrosine phosphorylation-regulated kinases (DYRK) exert a strong anti-herpesviral activity - Hutterer, Corina; Milbradt, Jens; Hamilton, Stuart; Zaja, Mirko; Leban, Johann; Henry, Christophe; Vitt, Daniel; Steingruber, Mirjam; Sonntag, Eric; Zeitträger, Isabel; Bahsi, Hanife; Stamminger, Thomas; et al. (Antiviral Research, 2017)
Infection with human cytomegalovirus (HCMV) is a serious medical problem, particularly in immunocompromised individuals and neonates. The success of (val)ganciclovir therapy is hampered by low drug compatibility and induction of viral resistance. A novel strategy of antiviral treatment is based on the exploitation of cell-directed signaling, e. g. pathways with a known relevance for carcinogenesis and tumor drug development. Here we describe a principle for putative antiviral drugs based on targeting dual-specificity tyrosine phosphorylation-regulated kinases (DYRKs). DYRKs constitute an evolutionarily conserved family of protein kinases with key roles in the control of cell proliferation and differentiation. Members of the DYRK family are capable of phosphorylating a number of substrate proteins, including regulators of the cell cycle, e.g. DYRK1B can induce cell cycle arrest, a critical step for the regulation of HCMV replication. Here we provide first evidence for a critical role of DYRKs during viral replication and the high antiviral potential of DYRK inhibitors (SC84227, SC97202 and SC97208, Harmine and AZ-191). Using established replication assays for laboratory and clinically relevant strains of HCMV, concentration-dependent profiles of inhibition were obtained. Mean inhibitory concentrations (EC50) of 0.98 ± 0.08 μM/SC84227, 0.60 ± 0.02 μM/SC97202, 6.26 ± 1.64 μM/SC97208, 0.71 ± 0.019 μM/Harmine and 0.63 ± 0.23 μM/AZ-191 were determined with HCMV strain AD169-GFP for the infection of primary human fibroblasts. A first analysis of the mode of antiviral action suggested a block of viral replication at the early-late stage of HCMV gene expression. Moreover, rhesus macaque cytomegalovirus (RhCMV), varicella-zoster virus (VZV) and herpes simplex virus (HSV-1) showed a similarly high sensitivity to these compounds. Thus, we conclude that DYRK signaling represents a promising target pathway for the development of novel anti-herpesviral strategies.
EVALuna2:33759

Innate nuclear sensor IFI16 translocates into the cytoplasm during the early stage of in vitro human cytomegalovirus infection and is entrapped in the egressing virions during the late stage - Dell'Oste, Valentina; Gatti, Deborah; Gugliesi, Francesca; De Andrea, Marco; Bawadekar, Mandar; Lo Cigno, Irene; Biolatti, Matteo; Vallino, Marta; Marschall, Manfred; Gariglio, Marisa; Landolfo, Santo (Journal of Virology, 2014)
Intrinsic immune mechanisms mediated by constitutively expressed proteins termed "restriction factors" provide frontline antiviral defense. We recently demonstrated that the DNA sensor IFI16 restricts human cytomegalovirus (HCMV) replication by downregulating viral early and late but not immediate-early mRNAs and their protein expression. We show here that at an early time point during the in vitro infection of low-passage-number human embryonic lung fibroblasts, IFI16 binds to HCMV DNA. However, during a later phase following infection, IFI16 is mislocalized to the cytoplasmic virus assembly complex (AC), where it colocalizes with viral structural proteins. Indeed, upon its binding to pUL97, IFI16 undergoes phosphorylation and relocalizes to the cytoplasm of HCMV-infected cells. ESCRT (endosomal sorting complex required for transport) machinery regulates the translocation of IFI16 into the virus AC by sorting and trafficking IFI16 into multivesicular bodies (MVB), as demonstrated by the interaction of IFI16 with two MVB markers: Vps4 and TGN46. Finally, IFI16 becomes incorporated into the newly assembled virions as demonstrated by Western blotting of purified virions and electron microscopy. Together, these results suggest that HCMV has evolved mechanisms to mislocalize and hijack IFI16, trapping it within mature virions. However, the significance of this IFI16 trapping following nuclear mislocalization remains to be established.Intracellular viral DNA sensors and restriction factors are critical components of host defense, which alarm and sensitize immune system against intruding pathogens. We have recently demonstrated that the DNA sensor IFI16 restricts human cytomegalovirus (HCMV) replication by downregulating viral early and late but not immediate-early mRNAs and their protein expression. However, viruses are known to evolve numerous strategies to cope and counteract such restriction factors and neutralize the first line of host defense mechanisms. Our findings describe that during early stages of infection, IFI16 successfully recognizes HCMV DNA. However, in late stages HCMV mislocalizes IFI16 into the cytoplasmic viral assembly complex and finally entraps the protein into mature virions. We clarify here the mechanisms HCMV relies to overcome intracellular viral restriction, which provides new insights about the relevance of DNA sensors during HCMV infection.
EVALuna2:8250

Investigational Antiviral Therapy Models for the Prevention and Treatment of Congenital Cytomegalovirus Infection during Pregnancy - Hamilton, Stuart T.; Marschall, Manfred; Rawlinson, William D. (Antimicrobial Agents and Chemotherapy, 2021)
Congenital cytomegalovirus (HCMV) infection may cause significant fetal malformation, lifelong disease, and, in severe cases, fetal or neonatal death. Placental infection with HCMV is the major mechanism of mother-to-child transmission (MTCT) and fetal injury. Thus, any pharmaceutical antiviral interference to reduce viral load may reduce placental damage, MTCT, and fetal disease. However, there is currently no licensed HCMV antiviral for use during pregnancy. In this study, aciclovir and the HCMV-specific antivirals letermovir, maribavir, and cidofovir were compared with ganciclovir for antiviral effects in model systems of pregnancy, including first-trimester TEV-1 trophoblast cell cultures and third-trimester ex vivo placental explant histocultures. HCMV-infected trophoblasts at 7 days postinfection (dpi) showed an EC50 of 21 mu M for aciclovir, 0.0007 mu M for letermovir, 0.11 mu M for maribavir, and 0.29 mu M for cidofovir, relative to 0.42 mu M for ganciclovir. Antivirals added at 10 mu M showed no cytotoxic effects and did not affect trophoblast cell proliferation (P > 0.9999). Multiple-round HCMV replication measured at 7 dpi showed letermovir, maribavir, and cidofovir treatment inhibited immediate early, early, and true late viral protein expression as assayed on Western blots. Antiviral treatment of HCMV-infected placental explants showed significant inhibition (P < 0.05) of viral replication with letermovir (83.3%), maribavir (83.6%), cidofovir (89.3%), and ganciclovir (82.4%), but not aciclovir (P > 0.9999). In ex vivo model systems, recently trialed HCMV antivirals letermovir and maribavir were effective at inhibiting HCMV replication. They partly fulfil requirements for use as safe and effective therapeutics during pregnancy to control congenital HCMV. Clinical trials of these newer agents would assist assessment of their utility in pregnancy.
CRIS-Team WoS Importer:2021-01-15

In vivo proof-of-concept for two experimental antiviral drugs, both directed to cellular targets, using a murine cytomegalovirus model - Sonntag, Eric; Hahn, Friedrich; Bertzbach, Luca D.; Seyler, Lisa; Wangen, Christina; Müller, Regina; Tannig, Pierre; Grau, Benedikt; Baumann, Matthias; Zent, Eldar; Zischinsky, Gunther; Eickhoff, Jan; et al. (Antiviral Research, 2019)
Infections with the human cytomegalovirus (HCMV) cause serious medical problems including organ rejection and congenital infection. Treatment of HCMV infections with currently available medication targeting viral enzymes is often accompanied with severe side effects and the occurrence of drug-resistant viruses. This demands novel therapeutical approaches like targeting genetically stable host cell proteins that are crucial for virus replication. Although numerous experimental drugs with promising in vitro efficacy have been identified, the lack of available data in animal models limits their potential for further clinical development. Recently, we described the very strong in vitro antiherpesviral activity of the NF-κB inhibitor TF27 and the CDK7 inhibitor LDC4297 at low nanomolar concentrations. In the present study, we present first data for the in vivo efficacy of both experimental drugs using an established cytomegalovirus animal model (murine CMV replication in immunodefective Rag −/− mice). The main findings of this study are (i) a strong inhibitory potency against beta- and gamma-herpesviruses of both compounds in vitro, (ii) even more important, a pronounced anticytomegaloviral activity also exerted in vivo, that resulted from (iii) a restriction of viral replication to the site of infection, thus preventing organ dissemination, (iv) in the absence of major compound-associated adverse events. Thus, we provide evidence for a strong antiviral potency in vivo and proof-of-concept for both drugs, which may encourage their further drug development, possibly including pharmacologically optimized derivatives, for a potential use in future antiherpesviral treatment.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Antiviral drug development; Antiviral experimental drugs; Artemisinin and pyrazolotriazine compounds; Herpesviral in vitro/vivo models; Human and murine cytomegaloviruses; Proof-of-concept

(Iso)Quinoline–Artemisinin Hybrids Prepared through Click Chemistry: Highly Potent Agents against Viruses - Capci Karagöz, Aysun; Lorion, Mélanie M.; Mai, Christina; Hahn, Friedrich; Hodek, Jan; Wangen, Christina; Weber, Jan; Marschall, Manfred; Ackermann, Lutz; Tsogoeva, Svetlana (Chemistry - A European Journal, 2020)
Viral infections cause life-threatening diseases in millions of people worldwide every year and there is an urgent need for new, effective antiviral drugs. Hybridization of two chemically diverse compounds into a new bioactive effector product is a successful concept to improve the properties of a hybrid drug relative to the parent compounds. In this study, (iso)quinoline–artemisinin hybrids, obtained through copper-catalyzed azide–alkyne cycloaddition or metal-free click reactions (in organic solvents or in the presence of water), were analyzed in vitro, for the first time, for their inhibitory activity against human cytomegalovirus (HCMV), relative to their parent compounds and the reference drug ganciclovir. EC50 (HCMV) values were obtained in a range 0.22–1.20 μm, which indicated highly potent antiviral properties in the absence of cytotoxic effects on normal cells (CC50>100 μm). The most active hybrid, 1 (EC50=0.22 μm), is 25 times more potent than its parent compound artesunic acid (EC50=5.41 μm) and 12 times more efficient than the standard drug ganciclovir (EC50=2.6 μm). Interestingly, hybrid 1 also shows inhibitory activity against hepatitis B virus in vitro (EC50 (HBeAg)=2.57 μm).
CRIS-Team Scopus Importer:2020-08-28
Keywords: antiviral agents; artemisinins; click chemistry; cycloaddition; quinolines

Light-Driven Catalyst-Free Access to Phthalazines: Entry to Antiviral Model Drugs by Merging Domino Reactions - Guryev, Anton; Schuster, Florian; Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Hodek, Jan; Weber, Jan; Marschall, Manfred; Tsogoeva, Svetlana (European Journal of Organic Chemistry, 2022)
We report the development of a metal-free four-step one-pot synthetic strategy to access high-value functionalized phthalazines using o-methyl benzophenones as starting compounds. Combining a light-mediated enolization of o-methyl benzophenones/Diels-Alder reaction domino process with a subsequent deprotection/aromatization domino reaction in one-pot leads to sustainable and efficient organic synthesis. The tangible advantages, i. e., absence of catalysts or additives, utilization of commercially available and/or easily accessible substrates, mild reaction conditions, simplicity, and single work-up procedure, make this combined process highly appealing for the direct construction of various 1-aryl-phthalazines. Importantly, in vitro bioactivity evaluation of these newly prepared heterocyclic compounds demonstrated a strong antiviral efficacy against major human pathogens like HCMV and SARS-CoV-2.
CRIS-Team WoS Importer:2022-11-18

Mass spectrometry-based characterization of the virion proteome, phosphoproteome, and associated kinase activity of human cytomegalovirus - Couté, Yohann; Kraut, Alexandra; Zimmermann, Christine; Büscher, Nicole; Hesse, Anne Marie; Bruley, Christophe; De Andrea, Marco; Wangen, Christina; Hahn, Friedrich; Marschall, Manfred; Plachter, Bodo (Microorganisms, 2020)
The assembly of human cytomegalovirus (HCMV) virions is an orchestrated process that requires, as an essential prerequisite, the complex crosstalk between viral structural proteins. Currently, however, the mechanisms governing the successive steps in the constitution of virion protein complexes remain elusive. Protein phosphorylation is a key regulator determining the sequential changes in the conformation, binding, dynamics, and stability of proteins in the course of multiprotein assembly. In this review, we present a comprehensive map of the HCMV virion proteome, including a refined view on the virion phosphoproteome, based on previous publications supplemented by new results. Thus, a novel dataset of viral and cellular proteins contained in HCMV virions is generated, providing a basis for future analyses of individual phosphorylation steps and sites involved in the orchestrated assembly of HCMV virion-specific multiprotein complexes. Finally, we present the current knowledge on the activity of pUL97, the HCMV-encoded and virion-associated kinase, in phosphorylating viral and host proteins.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Human cytomegalovirus; Mass spectrometry-based proteomics; Phosphorylation; Proteins; Virion composition; Virionassociated kinase

Methodological development of a multi-readout assay for the assessment of antiviral drugs against sars-cov-2 - Hahn, Friedrich; Häge, Sigrun; Herrmann, Alexandra; Wangen, Christina; Kicuntod, Jintawee; Jungnickl, Doris; Tillmanns, Julia; Müller, Regina; Fraedrich, Kirsten; Überla, Klaus; Kohlhof, Hella; Enßer, Armin; et al. (Pathogens, 2021)
Currently, human infections with the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) are accelerating the ongoing spread of the pandemic. Several innovative types of vaccines have already been developed, whereas effective options of antiviral treatments still await a scientific implementation. The development of novel anti-SARS-CoV-2 drug candidates demands skillful strategies and analysis systems. Promising results have been achieved with first generation direct-acting antivirals targeting the viral polymerase RdRp or the protease 3CLpro . Such recently approved or investigational drugs like remdesivir and GC376 represent a basis for further development and optimization. Here, we establish a multi-readout assay (MRA) system that enables the antiviral assessment and mechanistic characterization of novel test compounds, drug repurposing and combination treatments. Our SARS-CoV-2-specific MRA combines the quantitative measurement of several parameters of virus infection, such as the intracellular production of proteins and genomes, enzymatic activities and virion release, as well as the use of reporter systems. In this regard, the antiviral efficacy of remdesivir and GC376 has been investigated in human Caco-2 cells. The readouts included the use of spike-and double-strand RNA-specific monoclonal antibodies for in-cell fluorescence imaging, a newly generated recombinant SARS-CoV-2 reporter virus d6YFP, the novel 3CLpro-based FRET CFP::YFP and the previously reported FlipGFP reporter assays, as well as viral genome-specific RT-qPCR. The data produced by our MRA confirm the high antiviral potency of these two drugs in vitro. Combined, this MRA approach may be applied for broader analyses of SARS-CoV-2-specific antivirals, including compound screenings and the characterization of selected drug candidates.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Anti-coronaviral treatment; Antiviral drug assessment; Candidate drugs; COVID-19 pandemic; Cultured human cells; Methodological development; Multi-readout assay (MRA); SARS-CoV-2 infection

New Assay Systems to Characterize the Broad-Spectrum Antiherpesviral and Non-Herpesviral Activity of Cyclin-Dependent Kinase (CDK) 8 Inhibitors - Obergfäll, Debora; Hahn, Friedrich; Kicuntod, Jintawee; Wangen, Christina; Kögler, Melanie; Wagner, Sabrina; Kaufer, Benedikt; Marschall, Manfred (Pharmaceuticals, 2025)
Background. To date, a number of human pathogenic viruses are still unaddressed by the current repertoire of approved antiviral drugs. In order to widen this spectrum of preventive measures against virus infections, we have focused on additional host targets that exert interesting virus-supportive functions. Inhibitors of cyclin-dependent kinase 8 (CDK8) have been found to exhibit highly pronounced and relatively broad antiviral activity. Objectives. The current research question concerning the potential for broad-spectrum antiviral drug activity should be addressed in detail to understand the mechanistic basis of the antiviral target function of CDK8. Materials and Methods. We established and specifically customized six assay systems, three of these newly developed for the present study, to corroborate the range of CDK8 inhibitors’ antiviral activity against four α-, β-, and γ-herpesviruses as well as two non-herpesviruses. Results. Similar to our earlier analysis of CDK7 and CDK9 inhibitors, the clinically relevant CDK8 inhibitors currently in use demonstrated antiherpesviral activity in cell-culture-based infection models. Interestingly, the antiviral efficacy against various human and animal cytomegaloviruses was particularly strong at nanomolar concentrations, whereas other herpesviruses or non-herpesviruses showed an intermediate or low sensitivity to CDK8 inhibitors. Thus, this approach provided novel insights into the inhibitory potential of the CDK8 inhibitors, such as CCT-251921, MSC-2530818, and BI-1347, when analyzed against equine herpesvirus 1 (EHV-1, α-herpesvirus), human herpesvirus 6A (HHV-6A, β), Epstein–Barr virus (EBV, γ), murine herpesvirus 68 (MHV-68, γ), vaccinia virus (VV, non-herpes DNA virus), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, non-herpes RNA virus). Conclusions. Our results confirm that drug sensitivity to CDK8 inhibitors, on the one hand, is very strong for certain viruses and, on the other hand, varies widely within the spectrum of viruses and host cell types analyzed. This suggests that CDK8 may play several different roles in viral replication. The option of a refined CDK8-specific antiviral drug targeting is discussed.
CRIS-Team Scopus Importer:2025-11-07
Keywords: antiviral drug discovery; broad-spectrum antiviral drugs; cyclin-dependent kinase 8 (CDK8); human pathogenic viruses; new antiviral assay systems; novel host target proteins; pharmacological CDK8 inhibitors; pronounced antiviral activity; α-; β-; γ-herpesviruses

New efficient artemisinin derived agents against human leukemia cells, human cytomegalovirus and Plasmodium falciparum: 2nd generation 1,2,4-trioxane-ferrocene hybrids. - Reiter, Christoph; Fröhlich, Tony; Zeino, Maen; Marschall, Manfred; Bahsi, Hanife; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Hampel, Frank; Efferth, Thomas; Tsogoeva, Svetlana (European journal of medicinal chemistry, 2015)
In our ongoing search for highly active hybrid molecules exceeding their parent compounds in anticancer, antimalaria as well as antiviral activity and being an alternative to the standard drugs, we present the synthesis and biological investigations of 2nd generation 1,2,4-trioxane-ferrocene hybrids. In vitro tests against the CCRF-CEM leukemia cell line revealed di-1,2,4-trioxane-ferrocene hybrid 7 as the most active compound (IC50 of 0.01 μM). Regarding the activity against the multidrug resistant subline CEM/ADR5000, 1,2,4-trioxane-ferrocene hybrid 5 showed a remarkable activity (IC50 of 0.53 μM). Contrary to the antimalaria activity of hybrids 4-8 against Plasmodium falciparum 3D7 strain with slightly higher IC50 values (between 7.2 and 30.2 nM) than that of their parent compound DHA, hybrids 5-7 possessed very promising activity (IC50 values lower than 0.5 μM) against human cytomegalovirus (HCMV). The application of 1,2,4-trioxane-ferrocene hybrids against HCMV is unprecedented and demonstrated here for the first time.
Keywords: Artemisinin; Ferrocene; Hybrid; Cancer; Malaria; Human cytomegalovirus

New insight into the phosphorylation-regulated intranuclear localization of human cytomegalovirus pUL69 mediated by cyclin-dependent kinases (CDKs) and viral CDK orthologue pUL97 - Graf, Laura; Feichtinger, Sabine; Naing, Zin; Hutterer, Corina; Milbradt, Jens; Webel, Rike; Wagner, Sabrina; Scott, Gillian M.; Hamilton, Stuart T.; Rawlinson, William D.; Stamminger, Thomas; Thomas, Marco; et al. (Journal of General Virology, 2016)
Cyclin-dependent kinases (CDKs) are multifaceted regulators involved in the replication of human cytomegalovirus. Recently, we demonstrated an interaction of CDK9-cyclin T1 as well as viral CDK orthologue pUL97 with the viral regulator pUL69, thereby leading to pUL69-activating phosphorylation. Here, we demonstrate that colocalization and direct pUL69-cyclin T1 interaction is independent of viral strains and host cell types. In vitro phosphorylation of pUL69 by CDK9 or pUL97 did not occur in a single site-specific manner, but at multiple sites. The previously described fine-speckled nuclear aggregation of pUL69 was assigned to the late phase of viral replication. CDK inhibitors, including a novel inhibitor of the CDK-activating kinase CDK7, massively intensified this fine-speckled accumulation. Interestingly, we also observed spontaneous pUL69 accumulation in the absence of inhibitors at a lower frequency. These findings provide new insight into pUL69 kinase interregulation and emphasize the importance of pUL69 phosphorylation for correct intranuclear localization.
EVALuna2:8332

Novel cytomegalovirus-inhibitory compounds of the class pyrrolopyridines show a complex pattern of target binding that suggests an unusual mechanism of antiviral activity - Hahn, Friedrich; Hutterer, Corina; Henry, Christophe; Hamilton, Stuart T.; Strojan, Hanife; Kraut, Alexandra; Schulte, Ulrike; Schuetz, Martin; Kohrt, Stephan; Wangen, Christina; Pfizer, Jose; Coute, Yohann; et al. (Antiviral Research, 2018)
Human cytomegalovirus (HCMV) is a major human pathogen with seropositivity rates in the adult population ranging between 40% and 95%. HCMV infection is associated with severe pathology, such as life-threatening courses of infection in immunocompromised individuals and neonates. Current standard therapy with valganciclovir has the disadvantage of adverse side effects and viral drug resistance. A novel anti-HCMV drug, letermovir, has been approved recently, so that improved therapy options are available. Nevertheless, even more so far unexploited classes of compounds and molecular modes of action will be required for a next generation of antiherpesviral treatment strategies. In this study, we focused on the analysis of the antiviral potency of a novel class of compounds, i.e. pyrrolopyridine analogs, and identified both hit compounds and their target protein candidates. In essence, we provide novel evidence as follows: (i) screening hit SC88941 is highly active in inhibiting HCMV replication in primary human fibroblasts with an EC50 value of 0.20 +/- 0.01 mu M in the absence of cytotoxicity, (ii) inhibition occurs at the early-late stage of viral protein production and shows reinforcing effects upon LMV cotreatment, (iii) among the viruses analyzed, antiviral activity was most pronounced against beta-herpesviruses (HCMV, HHV-6A) and intermediate against adenovirus (HAdV-2), (iv) induction of SC88941 resistance was not detectable, thus differed from the induction of ganciclovir resistance, (v) a linker-coupled model compound was used for mass spectrometry-based target identification, thus yielding several drug-binding target proteins and (vi) a first confocal imaging approach used for addressing intracellular effects of SC88941 indicated qualitative and quantitative alteration of viral protein expression and localization. Thus, our findings suggest a multifaceted pattern of compound-target binding in connection with an unusual mode of action, opening up further opportunities of antiviral drug development.
EVALuna2:35263

Nuclear Egress Complexes of HCMV and Other Herpesviruses: Solving the Puzzle of Sequence Coevolution, Conserved Structures and Subfamily-Spanning Binding Properties - Marschall, Manfred; Häge, Sigrun; Conrad, Marcus; Alkhashrom, Sewar; Kicuntod, Jintawee; Schweininger, Johannes; Kriegel, Mark; Loesing, Josephine; Tillmanns, Julia; Neipel, Frank; Eichler, Jutta; Muller, Yves; et al. (Viruses, 2020)
Herpesviruses uniquely express two essential nuclear egress-regulating proteins forming a heterodimeric nuclear egress complex (core NEC). These core NECs serve as hexameric lattice-structured platforms for capsid docking and recruit viral and cellular NEC-associated factors that jointly exert nuclear lamina as well as membrane-rearranging functions (multicomponent NEC). The regulation of nuclear egress has been profoundly analyzed for murine and human cytomegaloviruses (CMVs) on a mechanistic basis, followed by the description of core NEC crystal structures, first for HCMV, then HSV-1, PRV and EBV. Interestingly, the highly conserved structural domains of these proteins stand in contrast to a very limited sequence conservation of the key amino acids within core NEC-binding interfaces. Even more surprising, although a high functional consistency was found when regarding the basic role of NECs in nuclear egress, a clear specification was identified regarding the limited, subfamily-spanning binding properties of core NEC pairs and NEC multicomponent proteins. This review summarizes the evolving picture of the relationship between sequence coevolution, structural conservation and properties of NEC interaction, comparing HCMV to alpha-, beta- and gamma-herpesviruses. Since NECs represent substantially important elements of herpesviral replication that are considered as drug-accessible targets, their putative translational use for antiviral strategies is discussed.
CRIS-Team WoS Importer:2020-08-07

Nuclear import of isoforms of the cytomegalovirus kinase pUL97 is mediated by differential activity of NLS1 and NLS2 both acting through classical importin-? binding - Webel, Rike; Solbak, Sara M. O.; Held, Christian; Milbradt, Jens; Groß, Andrea; Eichler, Jutta; Wittenberg, Thomas; Jardin, Christophe; Sticht, Heinrich; Fossen, Torgils; Marschall, Manfred (Journal of General Virology, 2012)
The multifunctional protein kinase pUL97 of human cytomegalovirus (HCMV) strongly determines the efficiency of virus replication. Previously, the existence of two pUL97 isoforms that arise from alternative translational initiation and show a predominant nuclear localization was described. Two bipartite nuclear localization sequences, NLS1 and NLS2, were identified in the N terminus of the large isoform, whilst the small isoform exclusively contained NLS2. The current study found the following: (i) pUL97 nuclear localization in HCMV-infected primary fibroblasts showed accumulations in virus replication centres and other nuclear sections; (ii) in a quantitative evaluation system for NLS activity, the large isoform showed higher efficiency of nuclear translocation than the small isoform; (iii) NLS1 was mapped to aa 6-35 and NLS2 to aa 190-213; (iv) using surface plasmon resonance spectroscopy, the binding of both NLS1 and NLS2 to human importin-? was demonstrated, stressing the importance of individual arginine residues in the bipartite consensus motifs; (v) nuclear magnetic resonance spectroscopy of pUL97 peptides confirmed an earlier statement about the functional requirement of NLS1 embedding into an intact ?-helical structure; and (vi) a bioinformatics investigation of the solvent-accessible surface suggested a high accessibility of NLS1 and an isoform-specific, variable accessibility of NLS2 for interaction with importin-?. Thus, the nucleocytoplasmic transport mechanism of the isoforms appeared to be differentially regulated, and this may have consequences for isoform-dependent functions of pUL97 during virus replication.
EVALuna2:8160

Patient-derived cytomegaloviruses with different ganciclovir sensitivities from UL97 mutation retain their replication efficiency and some kinase activity in vitro - Wong, Diana D.; Van Zuylen, Wendy J.; Hamilton, Stuart T.; Steingruber, Mirjam; Sonntag, Eric; Marschall, Manfred; Rawlinson, William D. (Antimicrobial Agents and Chemotherapy, 2019)
Mutations in the cytomegalovirus UL97 kinase gene contribute to antiviral resistance. Mutations A594S and G598D from two clinical isolates were analyzed, and bacterial artificial chromosome (BAC)-engineered A594S recombinant cytomegalovirus exhibited a ganciclovir-resistant phenotype on plaque reduction. Viral replication was comparable to that of the wild type. Cell-based kinase activity and autophosphorylation of ectopically expressed proteins showed that mutants retained some kinase activity. This study showed that patient-derived cytomegalovirus with different ganciclovir sensitivities retained replication efficiency and exhibited some kinase activity in vitro.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Cytomegalovirus; Drug resistance; Ganciclovir; Mutation; Phosphorylation; Protein kinase; UL97

Patterns of autologous and nonautologous interactions between core nuclear egress complex (NEC) proteins of α‐, β‐ and γ‐herpesviruses - Häge, Sigrun; Sonntag, Eric; Borst, Eva Maria; Tannig, Pierre; Seyler, Lisa; Bäuerle, Tobias; Bailer, Susanne M.; Lee, Chung Pei; Müller, Regina; Wangen, Christina; Milbradt, Jens; Marschall, Manfred (Viruses, 2020)
Nuclear egress is a regulated process shared by α‐, β‐ and γ‐herpesviruses. The core nuclear egress complex (NEC) is composed of the membrane‐anchored protein homologs of human cytomegalovirus (HCMV) pUL50, murine cytomegalovirus (MCMV) pM50, Epstein–Barr virus (EBV) BFRF1 or varicella zoster virus (VZV) Orf24, which interact with the autologous NEC partners pUL53, pM53, BFLF2 or Orf27, respectively. Their recruitment of additional proteins leads to the assembly of a multicomponent NEC, coordinately regulating viral nucleocytoplasmic capsid egress. Here, the functionality of VZV, HCMV, MCMV and EBV core NECs was investigated by coimmunoprecipitation and confocal imaging analyses. Furthermore, a recombinant MCMV, harboring a replacement of ORF M50 by UL50, was analyzed both in vitro and in vivo. In essence, core NEC interactions were strictly limited to autologous NEC pairs and only included one measurable nonautologous interaction between the homologs of HCMV and MCMV. A comparative analysis of MCMV‐WT versus MCMV‐UL50‐infected murine fibroblasts revealed almost identical phenotypes on the levels of protein and genomic replication kinetics. In infected BALB/c mice, virus spread to lung and other organs was found comparable between these viruses, thus stating functional complementarity. In conclusion, our study underlines that herpesviral core NEC proteins are functionally conserved regarding complementarity of core NEC interactions, which were found either virus‐specific or restricted within subfamilies.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Autologous vs. nonautologous interactions; Core NEC interaction properties; Core nuclear egress complexes (NECs); Degree of conservation; Functional complementarity; Multicomponent NEC recruitment of proteins; Takeover of activities in vitro and in vivo; α‐; β‐ and γ‐herpesviruses

Phenotypical Characterization of the Nuclear Egress of Recombinant Cytomegaloviruses Reveals Defective Replication upon ORF-UL50 Deletion but Not pUL50 Phosphosite Mutation - Häge, Sigrun; Sonntag, Eric; Svrlanska, Adriana; Borst, Eva Maria; Stilp, Anne Charlotte; Horsch, Deborah; Müller, Regina; Kropff, Barbara; Milbradt, Jens; Stamminger, Thomas; Schlötzer-Schrehardt, Ursula; Marschall, Manfred (Viruses, 2021)
Nuclear egress is a common herpesviral process regulating nucleocytoplasmic capsid release. For human cytomegalovirus (HCMV), the nuclear egress complex (NEC) is determined by the pUL50-pUL53 core that regulates multicomponent assembly with NEC-associated proteins and capsids. Recently, NEC crystal structures were resolved for α-, β- and γ-herpesviruses, revealing profound structural conservation, which was not mirrored, however, by primary sequence and binding properties. The NEC binding principle is based on hook-into-groove interaction through an N-terminal hook-like pUL53 protrusion that embraces an α-helical pUL50 binding groove. So far, pUL50 has been considered as the major kinase-interacting determinant and massive phosphorylation of pUL50-pUL53 was assigned to NEC formation and functionality. Here, we addressed the question of phenotypical changes of ORF-UL50-mutated HCMVs. Surprisingly, our analyses did not detect a predominant replication defect for most of these viral mutants, concerning parameters of replication kinetics (qPCR), viral protein production (Western blot/CoIP) and capsid egress (confocal imaging/EM). Specifically, only the ORF-UL50 deletion rescue virus showed a block of genome synthesis during late stages of infection, whereas all phosphosite mutants exhibited marginal differences compared to wild-type or revertants. These results (i) emphasize a rate-limiting function of pUL50 for nuclear egress, and (ii) demonstrate that mutations in all mapped pUL50 phosphosites may be largely compensated. A refined mechanistic concept points to a multifaceted nuclear egress regulation, for which the dependence on the expression and phosphorylation of pUL50 is discussed.
CRIS-Team Scopus Importer:2021-02-19
Keywords: core nuclear egress complex; differential functional relevance; human cytomegalovirus; ORF-UL50 deletion; phenotypical changes; pUL50 phosphosite mutants

Phosphosite Analysis of the Cytomegaloviral mRNA Export Factor pUL69 Reveals Serines with Critical Importance for Recruitment of Cellular Proteins Pin1 and UAP56/URH49 - Thomas, Marco; Müller, Regina; Horn, Georg; Bogdanow, Boris; Imami, Koshi; Milbradt, Jens; Steingruber, Mirjam; Marschall, Manfred; Schilling, Eva Maria; Fossen, Torgils; Stamminger, Thomas (Journal of Virology, 2020)
Human cytomegalovirus (HCMV) encodes the viral mRNA export factor pUL69, which facilitates the cytoplasmic accumulation of mRNA via interaction with the cellular RNA helicase UAP56 or URH49. We reported previously that pUL69 is phosphorylated by cellular CDKs and the viral CDK-like kinase pUL97. Here, we set out to identify phosphorylation sites within pUL69 and to characterize their importance. Mass spectrometry-based phosphosite mapping of pUL69 identified 10 serine/threonine residues as phosphoacceptors. Surprisingly, only a few of these sites localized to the N terminus of pUL69, which could be due to the presence of additional posttranslational modifications, like arginine methylation. As an alternative approach, pUL69 mutants with substitutions of putative phosphosites were analyzed by Phos-tag SDS-PAGE. This demonstrated that serines S46 and S49 serve as targets for phosphorylation by pUL97. Furthermore, we provide evidence that phosphorylation of these serines mediates cis/trans isomerization by the prolyl isomerase Pin1, thus forming a functional Pin1 binding motif. Surprisingly, while abrogation of the Pin1 motif did not affect the replication of recombinant cytomegaloviruses, mutation of serines next to the interaction site for UAP56/URH49 strongly decreased viral replication. This was correlated with a loss of UAP56/URH49 recruitment. Intriguingly, the critical serines S13 and S15 were located within a sequence resembling the UAP56 binding motif (UBM) of cellular mRNA adaptor proteins like REF and UIF. We propose that betaherpesviral mRNA export factors have evolved an extended UAP56/URH49 recognition sequence harboring phosphorylation sites to increase their binding affinities. This may serve as a strategy to successfully compete with cellular mRNA adaptor proteins for binding to UAP56/URH49.IMPORTANCE The multifunctional regulatory protein pUL69 of human cytomegalovirus acts as a viral RNA export factor with a critical role in efficient replication. Here, we identify serine/threonine phosphorylation sites for cellular and viral kinases within pUL69. We demonstrate that the pUL97/CDK phosphosites within alpha-helix 2 of pUL69 are crucial for its cis/trans isomerization by the cellular protein Pin1. Thus, we identified pUL69 as the first HCMV-encoded protein that is phosphorylated by cellular and viral serine/threonine kinases in order to serve as a substrate for Pin1. Furthermore, our study revealed that betaherpesviral mRNA export proteins contain extended binding motifs for the cellular mRNA adaptor proteins UAP56/URH49 harboring phosphorylated serines that are critical for efficient viral replication. Knowledge of the phosphorylation sites of pUL69 and the processes regulated by these posttranslational modifications is important in order to develop antiviral strategies based on a specific interference with pUL69 phosphorylation.
CRIS-Team Scopus Importer:2020-04-14
Keywords: herpesviruses; human cytomegalovirus; ICP27; mRNA export; protein phosphorylation; pUL69

Properties of Oligomeric Interaction of the Cytomegalovirus Core Nuclear Egress Complex (NEC) and Its Sensitivity to an NEC Inhibitory Small Molecule - Kicuntod, Jintawee; Alkhashrom, Sewar; Häge, Sigrun; Diewald, Benedikt; Müller, Regina; Hahn, Friedrich; Lischka, Peter; Sticht, Heinrich; Eichler, Jutta; Marschall, Manfred (Viruses, 2021)
Herpesviral nuclear egress is a regulated process shared by all family members, ensuring the efficient cytoplasmic release of viral capsids. In the case of human cytomegalovirus (HCMV), the core of the nuclear egress complex (NEC) consists of the pUL50-pUL53 heterodimer that builds hexameric lattices for capsid binding and multicomponent interaction, including NEC-associated host factors. A characteristic feature of NEC interaction is the N-terminal hook structure of pUL53 that binds to an alpha-helical groove of pUL50, thus termed as hook-into-groove interaction. This central regulatory element is essential for viral replication and shows structural-functional conservation, which has been postulated as a next-generation target of antiviral strategies. However, a solid validation of this concept has been missing. In the present study, we focused on the properties of oligomeric HCMV core NEC interaction and the antiviral activity of specifically targeted prototype inhibitors. Our data suggest the following: (i) transiently expressed, variably tagged versions of HCMV NEC proteins exert hook-into-groove complexes, putatively in oligomeric assemblies that are distinguishable from heterodimers, as shown by in vitro assembly and coimmunoprecipitation approaches; (ii) this postulated oligomeric binding pattern was further supported by the use of a pUL50::pUL53 fusion construct also showing a pronounced multi-interaction potency; (iii) using confocal imaging cellular NEC-associated proteins were found partly colocalized with the tagged core NECs; (iv) a small inhibitory molecule, recently identified by an in vitro binding inhibition assay, was likewise active in blocking pUL50-pUL53 oligomeric assembly and in exerting antiviral activity in HCMV-infected fibroblasts. In summary, the findings refine the previous concept of HCMV core NEC formation and nominate this drug-accessible complex as a validated antiviral drug target.
CRIS-Team WoS Importer:2021-04-09

Protein kinases responsible for the phosphorylation of the nuclear egress core complex of human cytomegalovirus - Sonntag, Eric; Milbradt, Jens; Svrlanska, Adriana; Strojan, Hanife; Haege, Sigrun; Kraut, Alexandra; Hesse, Anne-Marie; Amin, Bushra; Sonnewald, Uwe; Coute, Yohann; Marschall, Manfred (Journal of General Virology, 2017)
Nuclear egress of herpesvirus capsids is mediated by a multi-component nuclear egress complex (NEC) assembled by a heterodimer of two essential viral core egress proteins. In the case of human cytomegalovirus (HCMV), this core NEC is defined by the interaction between the membrane-anchored pUL50 and its nuclear cofactor, pUL53. NEC protein phosphorylation is considered to be an important regulatory step, so this study focused on the respective role of viral and cellular protein kinases. Multiply phosphorylated pUL50 varieties were detected by Western blot and Phos-tag analyses as resulting from both viral and cellular kinase activities. In vitro kinase analyses demonstrated that pUL50 is a substrate of both PKC alpha and CDK1, while pUL53 can also be moderately phosphorylated by CDK1. The use of kinase inhibitors further illustrated the importance of distinct kinases for core NEC phosphorylation. Importantly, mass spectrometry-based proteomic analyses identified five major and nine minor sites of pUL50 phosphorylation. The functional relevance of core NEC phosphorylation was confirmed by various experimental settings, including kinase knock-down/knock-out and confocal imaging, in which it was found that (i) HCMV core NEC proteins are not phosphorylated solely by viral pUL97, but also by cellular kinases; (ii) both PKC and CDK1 phosphorylation are detectable for pUL50; (iii) no impact of PKC phosphorylation on NEC functionality has been identified so far; (iv) nonetheless, CDK1-specific phosphorylation appears to be required for functional core NEC interaction. In summary, our findings provide the first evidence that the HCMV core NEC is phosphorylated by cellular kinases, and that the complex pattern of NEC phosphorylation has functional relevance.
Keywords: human cytomegalovirus; nuclear egress; core NEC; protein-protein interaction; cellular protein kinases; phosphorylation

Proteomic analysis of the multimeric nuclear egress complex of human cytomegalovirus - Milbradt, Jens; Kraut, Alexandra; Hutterer, Corina; Sonntag, Ellen; Schmeiser, Cathrin; Ferro, Myriam; Wagner, Sabrina; Lenac, Tihana; Claus, Claudia; Pinkert, Sandra; Hamilton, Stuart T.; Rawlinson, William D.; et al. (Molecular & Cellular Proteomics, 2014)
Herpesviral capsids are assembled in the host cell nucleus before being translocated into the cytoplasm for further maturation. The crossing of the nuclear envelope represents a major event that requires the formation of the nuclear egress complex (NEC). Previous studies demonstrated that human cytomegalovirus (HCMV) proteins pUL50 and pUL53, as well as their homologs in all members of Herpesviridae, interact with each other at the nuclear envelope and form the heterodimeric core of the NEC. In order to characterize further the viral and cellular protein content of the multimeric NEC, the native complex was isolated from HCMV-infected human primary fibroblasts at various time points and analyzed using quantitative proteomics. Previously postulated components of the HCMV-specific NEC, as well as novel potential NEC-associated proteins such as emerin, were identified. In this regard, interaction and colocalization between emerin and pUL50 were confirmed by coimmunoprecipitation and confocal microscopy analyses, respectively. A functional validation of viral and cellular NEC constituents was achieved through siRNA-mediated knockdown experiments. The important role of emerin in NEC functionality was demonstrated by a reduction of viral replication when emerin expression was down-regulated. Moreover, under such conditions, reduced production of viral proteins and deregulation of viral late cytoplasmic maturation were observed. Combined, these data prove the functional importance of emerin as an NEC component, associated with pUL50, pUL53, pUL97, p32/gC1qR, and further regulatory proteins. Summarized, our findings provide the first proteomics-based characterization and functional validation of the HCMV-specific multimeric NEC.
EVALuna2:8226

Proteomic interaction patterns between human cyclins, the cyclin-dependent kinase ortholog pUL97 and additional cytomegalovirus proteins - Steingruber, Mirjam; Kraut, Alexandra; Socher, Eileen; Sticht, Heinrich; Reichel, Anna; Stamminger, Thomas; Amin, Bushra; Coute, Yohann; Hutterer, Corina; Marschall, Manfred (Viruses, 2016)
The human cytomegalovirus (HCMV)-encoded cyclin-dependent kinase (CDK) ortholog pUL97 associates with human cyclin B1 and other types of cyclins. Here, the question was addressed whether cyclin interaction of pUL97 and additional viral proteins is detectable by mass spectrometry-based approaches. Proteomic data were validated by coimmunoprecipitation (CoIP), Western blot, in vitro kinase and bioinformatic analyses. Our findings suggest that: (i) pUL97 shows differential affinities to human cyclins; (ii) pUL97 inhibitor maribavir (MBV) disrupts the interaction with cyclin B1, but not with other cyclin types; (iii) cyclin H is identified as a new high-affinity interactor of pUL97 in HCMV-infected cells; (iv) even more viral phosphoproteins, including all known substrates of pUL97, are detectable in the cyclin-associated complexes; and (v) a first functional validation of pUL97-cyclin B1 interaction, analyzed by in vitro kinase assay, points to a cyclin-mediated modulation of pUL97 substrate preference. In addition, our bioinformatic analyses suggest individual, cyclin-specific binding interfaces for pUL97-cyclin interaction, which could explain the different strengths of interactions and the selective inhibitory effect of MBV on pUL97-cyclin B1 interaction. Combined, the detection of cyclin-associated proteins in HCMV-infected cells suggests a complex pattern of substrate phosphorylation and a role of cyclins in the fine-modulation of pUL97 activities.
Keywords: CDK ortholog pUL97; Cyclin-associated protein complexes; Human cyclins; Human cytomegalovirus; Molecular modeling; Proteomic analysis

Recombinant Human Cytomegalovirus Expressing an Analog-Sensitive Kinase pUL97 as Novel Tool for Functional Analyses - Krämer, Nadine; Schütz, Martin; Mato, Uxía Gestal; Herhaus, Lina; Marschall, Manfred; Zimmermann, Christine (Viruses, 2022)
The human cytomegalovirus (HCMV) is a member of the beta-herpesvirus family and inflicts life-long latent infections in its hosts. HCMV has been shown to manipulate and dysregulate many cellular processes. One major interactor with the cellular host is the viral kinase pUL97. The UL97 gene is essential for viral replication, and kinase-deficient mutants of pUL97 display a severe replication defect. Recently, another group established an analog-sensitive version of the pUL97 protein. This mutant kinase can be treated with a non-hydrolysable ATP analog, thereby inhibiting its kinase function. This process is reversible by removing the ATP analog by media change. We introduced this mutant version of the pUL97 protein into the laboratory strain Ad169 of HCMV, BADwt, creating a BAD-UL97-as1 viral mutant. This mutant virus replicated normally in infected cells in the absence of the ATP analog and maintained its ability to phosphorylate its cellular substrates. However, when treated with the ATP analog, BAD-UL97-as1 displayed a defect in the production of intra- and extracellular viral DNA and in the production of viral progeny. Furthermore, in the presence of 3MB-PP1, a well-established substrate of pUL97 was no longer hyperphosphorylated. This effect was detectable as early as 4 h post treatment, which allows for studies on pUL97 without the complication of low viral titers. Nevertheless, we observed off-target effects of 3MB-PP1 on several cellular processes, which should be considered with this approach.
CRIS-Team Scopus Importer:2022-11-04
Keywords: analog-sensitive pUL97 variant; BACmid-derived recombinant HCMV; functional analyses; human cytomegalovirus (HCMV); protein kinase pUL97; pUL97-specific inhibitors; viral kinase activity

'Shared-Hook' and 'Changed-Hook' Binding Activities of Herpesviral Core Nuclear Egress Complexes Identified by Random Mutagenesis - Lösing, Josephine; Haege, Sigrun; Schütz, Martin; Wagner, Sabrina; Wardin, Julia; Sticht, Heinrich; Marschall, Manfred (Cells, 2022)
Herpesviruses replicate their genomes and assemble their capsids in the host cell nucleus. To progress towards morphogenesis in the cytoplasm, herpesviruses evolved the strategy of nuclear egress as a highly regulated process of nucleo-cytoplasmic capsid transition. The process is conserved among alpha-, beta- and gamma-herpesviruses and involves the formation of a core and multicomponent nuclear egress complex (NEC). Core NEC is assembled by the interaction between the nucleoplasmic hook protein, i.e., pUL53 (human cytomegalovirus, HCMV), and the integral membrane-associated groove protein, i.e., pUL50. Our study aimed at the question of whether a panherpesviral NEC scaffold may enable hook-into-groove interaction across herpesviral subfamilies. For this purpose, NEC constructs were generated for members of all three subfamilies and analyzed for multi-ligand interaction using a yeast two-hybrid (Y2H) approach with randomized pUL53 mutagenesis libraries. The screening identified ten library clones displaying cross-viral shared hook-into-groove interaction. Interestingly, a slightly modified Y2H screening strategy provided thirteen further changed-hook pUL53 clones having lost parental pUL50 interaction but gained homolog interaction. In addition, we designed a sequence-predicted hybrid construct based on HCMV and Epstein-Barr virus (EBV) core NEC proteins and identified a cross-viral interaction phenotype. Confirmation was provided by applying protein-protein interaction analyses in human cells, such as coimmunoprecipitation settings, confocal nuclear rim colocalization assays, and HCMV Delta UL53 infection experiments with pUL53-complementing cells. Combined, the study provided the first examples of cross-viral NEC interaction patterns and revealed a higher yield of human cell-confirmed binding clones using a library exchange rate of 3.4 than 2.7. Thus, the study provides improved insights into herpesviral NEC protein binding specificities of core NEC formation. This novel information might be exploited to gain a potential target scaffold for the development of broadly acting NEC-directed inhibitory small molecules.
CRIS-Team WoS Importer:2023-01-27

Specific residues of a conserved domain in the N terminus of the human cytomegalovirus pUL50 protein determine its intranuclear interaction with pUL53 - Milbradt, Jens; Auerochs, Sabrina; Sevvana, Madhumati; Muller, Yves; Sticht, Heinrich; Marschall, Manfred (Journal of Biological Chemistry, 2012)
Herpesviral capsids are assembled in the host cell nucleus and are subsequently translocated to the cytoplasm. During this process it has been demonstrated that the human cytomegalovirus proteins pUL50 and pUL53 interact and form, together with other viral and cellular proteins, the nuclear egress complex at the nuclear envelope. In this study we provide evidence that specific residues of a conserved N-terminal region of pUL50 determine its intranuclear interaction with pUL53. In silico evaluation and biophysical analyses suggested that the conserved region forms a regular secondary structure adopting a globular fold. Importantly, site-directed replacement of individual amino acids by alanine indicated a strong functional influence of specific residues inside this globular domain. In particular, mutation of the widely conserved residues Glu-56 or Tyr-57 led to a loss of interaction with pUL53. Consistent with the loss of binding properties, mutants E56A and Y57A showed a defective function in the recruitment of pUL53 to the nuclear envelope in expression plasmid-transfected and human cytomegalovirus-infected cells. In addition, in silico analysis suggested that residues 3-20 form an amphipathic ?-helix that appears to be conserved among Herpesviridae. Point mutants revealed a structural role of this N-terminal ?-helix for pUL50 stability rather than a direct role in the binding of pUL53. In contrast, the central part of the globular domain including Glu-56 and Tyr-57 is directly responsible for the functional interaction with pUL53 and thus determines formation of the basic nuclear egress complex.
EVALuna2:8148

Stimulatory effects of human cytomegalovirus tegument protein pp71 lead to increased expression of CCL2 (monocyte chemotactic protein-1) during infection - Naing, Zin; Webel, Rike; Hamilton, Stuart; Schmeiser, Cathrin; Scott, Gillian; Marschall, Manfred; Rawlinson, William (Journal of General Virology, 2015)
Human cytomegalovirus (CMV) is the most common infectious cause of congenital birth defects in developed countries. Studies of infected amniotic fluid and placentae show CMV infection leads to a pro-inflammatory shift in cytokine profiles with implications for pathogenesis of foetal disease. ELISA, immunofluorescence and real-time-PCR assays were used to investigate CCL2 (monocyte chemotactic protein-1) and TNF-? changes following CMV infection of human fibroblasts, as well as following transient expression of CMV gene products in HeLa cells. Infection of human fibroblasts with CMV AD169 resulted in increased cytoplasmic and extracellular expression of CCL2 during early stages of infection, followed by marked downregulation of the chemokine at late times. Induction of CCL2 was not observed with CMV clinical strain Merlin, consistent with the postulated immune-evasion potential of this genetically intact WT strain. Comparison between live and UV-irradiated virus infections showed that changes in CCL2 levels were a direct response to active CMV replication. There were no significant changes in TNF-? expression during a parallel time-course of CMV infection. In transient transfection assays, overexpression of CMV tegument protein pp71 resulted in intracellular and extracellular upregulation of CCL2 protein. mRNA analysis showed that pp71-induced elevation in CCL2 was mediated through transcriptional upregulation. The data showed that CMV-induced upregulation of CCL2 during early stages of infection was mediated, at least in part, by stimulation of viral pp71, which may contribute to viral pathogenesis through enhanced virus dissemination.
EVALuna2:8267

Synthesis and Characterization of DHODH Inhibitors Based on the Vidofludimus Scaffold with Pronounced Anti-SARS-CoV-2 Activity - Gege, Christian; Hahn, Friedrich; Wangen, Christina; Häge, Sigrun; Herrmann, Alexandra; Uhlig, Nadja; Eberlein, Valentina; Issmail, Leila; Klopfleisch, Robert; Grunwald, Thomas; Marschall, Manfred; Kohlhof, Hella; et al. (ChemMedChem, 2024)
New strategies for the rapid development of broad-spectrum antiviral therapies are urgently required for emerging and re-emerging viruses like the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Host-directed antivirals that target universal cellular metabolic pathways necessary for viral replication present a promising approach with broad-spectrum activity and low potential for development of viral resistance. Dihydroorotate dehydrogenase (DHODH) was identified as one of those universal host factors essential for the replication of many clinically relevant human pathogenic viruses. DHODH is the rate-limiting enzyme catalyzing the fourth step in the de novo pyrimidine synthesis. Therefore, it is also developed as a therapeutic target for many diseases relying on cellular pyrimidine resources, such as cancer, autoimmune diseases and viral or bacterial infection. Thus, several DHODH inhibitors, including vidofludimus calcium (VidoCa, IMU-838), are currently in development or have been investigated in clinical trials for the treatment of virus infections such as SARS-CoV-2-mediated coronavirus disease 19 (COVID-19). Here, we report the medicinal chemistry optimization of VidoCa that resulted in metabolically more stable derivatives with improved DHODH target inhibition in various mammalian species, which translated into improved efficacy against SARS-CoV-2.
CRIS-Team Scopus Importer:2024-10-11
Keywords: antiviral agents; COVID-19; DHODH; host-directed antivirals; host-directed drug targeting; vidofludimus calcium; viruses

Synthesis, molecular features and biological activities of modified plant polysaccharides - Mukherjee, Shuvam; Jana, Subrata; Khawas, Sadhana; Kicuntod, Jintawee; Marschall, Manfred; Ray, Bimalendu; Ray, Sayani (Carbohydrate Polymers, 2022)
Plant polysaccharides represent a natural source material characterized by high ubiquity, abundance and biological activities that can be utilised as organic matter in numerous manufacturing processes including pharmaceutical. The goal-oriented modification of polysaccharides by chemical reactions brings about a substantial refinement in their molecular features and biological activity. An improved understanding of the intrinsic molecular features of plant polysaccharides, as well as the structure-activity relationship eventually caused by chemical alterations, may be fundamental for the development of technologies supporting their biomedical oriented exploitation. Herein, we attempt to provide a broader view on these topics and to illustrate methodologies of chemical modification. These are intended to enhance the functionality of plant polysaccharides, such as their modification-induced biological activities, finally making the products available for translational purposes.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Biological activities; Chemical modifications; Molecular features; Plant polysaccharides; Structure-activity relationship

Synthesis of Artemisinin-Derived Dimers, Trimers and Dendrimers: Investigation of Their Antimalarial and Antiviral Activities Including Putative Mechanisms of Action - Fröhlich, Tony; Hahn, Friedrich; Belmudes, Lucid; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Coute, Yohann; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2018)
Generation of dimers, trimers and dendrimers of bioactive compounds is an approach that has recently been developed for the discovery of new potent drug candidates. Herein, we present the synthesis of new artemisinin-derived dimers and dendrimers and investigate their action against malaria parasite Plasmodium falciparum 3D7 strain and human cytomegalovirus (HCMV). Dimer 7 was the most active compound (EC50 1.4 nm) in terms of antimalarial efficacy and was even more effective than the standard drugs dihydroartemisinin (EC50 2.4 nm), artesunic acid (EC50 8.9 nm) and chloroquine (EC50 9.8 nm). Trimer 4 stood out as the most active agent against HCMV in vitro replication and exerted an EC50 value of 0.026 mu m, representing an even higher activity than the two reference drugs ganciclovir (EC50 2.60 mu m) and artesunic acid (EC50 5.41 mu m). In addition, artemisinin-derived dimer 13 and trimer 15 were for the first time both immobilized on TOYOPEARL AF-Amino-650M beads and used for mass spectrometry-based target identification experiments using total lysates of HCMV-infected primary human fibroblasts. Two major groups of novel target candidates, namely cytoskeletal and mitochondrial proteins were obtained. Two putatively compound-binding viral proteins, namely major capsid protein (MCP) and envelope glycoprotein pUL132, which are both essential for HCMV replication, were identified.
EVALuna2:35275

Synthesis of Artemisinin-Estrogen Hybrids Highly Active against HCMV, P-falciparum, and Cervical and Breast Cancer - Fröhlich, Tony; Kiss, Anita; Wolfling, Janos; Mernyak, Erzsebet; Kulmany, Agnes E.; Minorics, Renata; Zupko, Istvan; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Hahn, Friedrich; Marschall, Manfred; et al. (ACS Medicinal Chemistry Letters, 2018)
Artemisinin-estrogen hybrids were for the first time both synthesized and investigated for their in vitro biological activity against malaria parasites (Plasmodium falciparum 3D7), human cytomegalovirus (HCMV), and a panel of human malignant cells of gynecological origin containing breast (MCF7, MDA-MB-231, MDA-MB-361, T47D) and cervical tumor cell lines (HeLa, SiHa, C33A). In terms of antimalarial efficacy, hybrid 8 (EC50 = 3.8 nM) was about two times more active than its parent compound artesunic acid (7) (EC50 = 8.9 nM) as well as the standard drug chloroquine (EC50 = 9.8 nM) and was, therefore, comparable to the clinically used dihydroartemisinin (6) (EC50 = 2.4 nM). Furthermore, hybrids 9-12 showed a strong antiviral effect with EC50 values in the submicromolar range (0.22-0.38 mu M) and thus possess profoundly stronger anti-HCMV activity (approximately factor 25) than the parent compound artesunic acid (7) (EC50 = 5.41 mu M). These compounds also exerted a higher in vitro anti-HCMV efficacy than ganciclovir used as the standard of current antiviral treatment. In addition, hybrids 8-12 elicited substantially more pronounced growth inhibiting action on all cancer cell lines than their parent compounds and the reference drug cisplatin. The most potent agent, hybrid 12, exhibited submicromolar EC50 values (0.15-0.93 mu M) against breast cancer and C33A cell lines.
EVALuna2:35262

Synthesis of new betulinic acid/betulin-derived dimers and hybrids with potent antimalarial and antiviral activities - Capci Karagöz, Aysun; Leidenberger, Maria; Hahn, Friedrich; Friedrich, Oliver; Hampel, Frank; Marschall, Manfred; Kappes, Bärbel; Tsogoeva, Svetlana (Bioorganic & Medicinal Chemistry, 2019)
Severe malaria and viral infections cause life-threatening diseases in millions of people worldwide every year. In search for effective bioactive hybrid molecules, which may possess improved properties compared to their parent compounds, a series of betulinic acid/betulin based dimer and hybrid compounds carrying ferrocene and/or artesunic acid moieties, was designed and, synthesized de novo. Furthermore, they were analyzed in vitro against malaria parasites (growth inhibition of 3D7-strain P. falciparum-infected erythrocytes) and human cytomegalovirus (HCMV). From this series of hybrids/dimers, the betulinic acid/betulin and artesunic acid hybrids 11 and 12 showed the most potent activities against P. falciparum and HCMV. On the strength of results, additive and/or synergistic effects between the natural or semisynthetic products, such as betulinic acid-/betulin- and artesunic acid-derived compounds, are suggested on the basis of putatively complex modes of antimicrobial action. This advantage may be taken into account in future drug development.
Keywords: Betulin; Betulinic acid; Artesunic acid; Ferrocene; Natural product hybrid; Antimalarial activity; Antiviral activity

Synthesis of Novel Hybrids of Quinazoline and Artemisinin with High Activities against Plasmodium falciparum, Human Cytomegalovirus, and Leukemia Cells - Fröhlich, Tony; Reiter, Christoph; Ibrahim, Mohammad M.; Beutel, Jannis; Hutterer, Corina; Zeitträger, Isabel; Bahsi, Hanife; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Efferth, Thomas; Marschall, Manfred; et al. (ACS Omega, 2017)
Many quinazoline derivatives have been synthesized over the last few decades with great pharmacological potential, such as antimalarial, anti-inflammatory, antimicrobial, anticancer, and antiviral. But so far, no quinazoline-artemisinin hybrids have been reported in the literature. In the present study, five novel quinazoline-artemisinin hybrids were synthesized and evaluated for their in vitro biological activity against malarial parasites (Plasmodium falciparum 3D7), leukemia cells (CCRF-CEM and CEM/ADR5000), and human cytomegalovirus. Remarkably, hybrid 9 (EC50 = 1.4 nM), the most active antimalarial compound of this study, was not only more potent than artesunic acid (EC50 = 9.7 nM) but at the same time more active than the clinically used drugs dihydroartemisinin (EC50 = 2.4 nM) and chloroquine (EC50 = 9.8 nM). Furthermore, hybrids 9 and 10 were the most potent compounds with regard to anticytomegaloviral activity (EC50 = 0.15-0.21 μM). They were able to outperform ganciclovir (EC50 = 2.6 μM), which is the relevant standard drug of antiviral therapy, by a factor of 12-17. Moreover, we identified a new highly active quinazoline derivative, compound 14, that is most effective in suppressing cytomegalovirus replication with an EC50 value in the nanomolar range (EC50 = 50 nM). In addition, hybrid 9 exhibited an antileukemia effect similar to that of artesunic acid, with EC50 values in the low micromolar range, and was 45 times more active toward the multidrug-resistant CEM/ADR5000 cells (EC50 = 0.5 μM) than the standard drug doxorubicin.
EVALuna2:35475

Target verification of artesunate-related antiviral drugs: Assessing the role of mitochondrial and regulatory proteins by click chemistry and fluorescence labeling - Hahn, Friedrich; Niesar, Aischa; Wangen, Christina; Wild, Markus; Grau, Benedikt; Herrmann, Lars; Capci, Aysun; Adrait, Annie; Couté, Yohann; Tsogoeva, Svetlana; Marschall, Manfred (Antiviral Research, 2020)
Human cytomegalovirus (HCMV) infection is associated with serious pathology such as transplant rejection or embryonic developmental defects. Antiviral treatment with currently available drugs targeting viral enzymes is often accompanied with severe side effects and the occurrence of drug-resistant viruses. For this reason, novel ways of anti-HCMV therapy focusing on so far unexploited small molecules, targets and mechanisms are intensively studied. Recently, we described the pronounced antiviral activity of the artesunate-related class of trioxane compounds, comprising NF-κB/signaling inhibitors like the trimeric derivative TF27, which proved to be highly active in a nanomolar range both in vitro and in vivo. Here, we extend this analysis by presenting further TF27/artesunate-derived antiviral compounds designed for their specific use in target verification by click chemistry applied in fluorescence labeling and tag affinity strategies. Our main findings are as follows: (i) compounds TF27, BG95, AC98 and AC173 exert strong inhibitory activity against HCMV replication in cultured primary human cells, (ii) autofluorescence activity could be quantitatively detected for BG95 and AC98, and confocal fluorescence imaging revealed accumulation in mitochondria, (iii) postulated cellular targets including mitochondrial proteins were down-regulated upon TF27 treatment, (iv) a click chemistry-based protocol of target enrichment was established, and (v) mass spectrometry-based proteomic analysis, using proteins from HCMV-infected fibroblasts covalently interacting with AC173, revealed a refined list of targets. Combined, data strongly suggest a complex mode of antiviral drug-target interaction of artesunate-related compounds, now highlighting potential roles of mitochondrial, NF-κB pathway proteins, exportins and possibly more. This strategy may further promote antiviral drug development on the basis of pharmacologically optimized trioxane derivatives.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Antiviral experimental drugs; Artemisinin compounds; Click chemistry; Human cytomegalovirus; Proteomics

The Artemisinin-Derived Autofluorescent Compound BG95 Exerts Strong Anticytomegaloviral Activity Based on a Mitochondrial Targeting Mechanism - Wild, Markus; Hahn, Friedrich; Grau, Benedikt; Herrmann, Lars; Niesar, Aischa; Schütz, Martin; Lorion, Melanie M.; Ackermann, Lutz; Tsogoeva, Svetlana; Marschall, Manfred (International Journal of Molecular Sciences, 2020)
Human cytomegalovirus (HCMV) is a major human pathogen associated with severe pathology. Current options of antiviral therapy only partly satisfy the needs of a well-tolerated long-term treatment/prophylaxis free from drug-induced viral resistance. Recently, we reported the strong antiviral properties in vitro and in vivo of the broad-spectrum anti-infective drug artesunate and its optimized derivatives. NF-κB signaling was described as a targeting mechanism and additional target proteins have recently been identified. Here, we analyzed the autofluorescent hybrid compound BG95, which could be utilized for intracellular visualization by confocal imaging and a tracking analysis in virus-infected primary human fibroblasts. As an important finding, BG95 accumulated in mitochondria visualized by anti-prohibitin and MitoTracker staining, and induced statistically significant changes of mitochondrial morphology, distinct from those induced by HCMV infection. Notably, mitochondrial membrane potential was found substantially reduced by BG95, an effect apparently counteracting efficient HCMV replication, which requires active mitochondria and upregulated energy levels. This finding was consistent with binding properties of artesunate-like compounds to mitochondrial proteins and thereby suggested a new mechanistic aspect. Combined, the present study underlines an important role of mitochondria in the multifaceted, host-directed antiviral mechanism of this drug class, postulating a new mitochondria-specific mode of protein targeting.
CRIS-Team Scopus Importer:2020-08-14
Keywords: antiviral drugs; artemisinin derivative; autofluorescence; human cytomegalovirus; intracellular tracking; mitochondrial architecture; mitochondrial impairment; mitochondrial targeting

The broad-spectrum antiinfective drug artesunate interferes with the canonical nuclear factor kappa B (NF-κB) pathway by targeting RelA/p65 - Hutterer, Corina; Niemann, Ina; Milbradt, Jens; Fröhlich, Tony; Reiter, Christoph; Kadioglu, Onat; Bahsi, Hanife; Zeitträger, Isabel; Wagner, Sabrina; Einsiedel, Jürgen; Gmeiner, Peter; Vogel, Nicolas; et al. (Antiviral Research, 2015)
Infection with human cytomegalovirus (HCMV) is a serious medical problem, particularly in immunocompromised individuals and neonates. The success of standard antiviral therapy is hampered by low drug compatibility and induction of viral resistance. A novel strategy is based on the exploitation of cell-directed signaling inhibitors. The broad antiinfective drug artesunate (ART) offers additional therapeutic options such as oral bioavailability and low levels of toxic side-effects. Here, novel ART-derived compounds including dimers and trimers were synthesized showing further improvements over the parental drug. Antiviral activity and mechanistic aspects were determined leading to the following statements: (i) ART exerts antiviral activity towards human and animal herpesviruses, (ii) no induction of ART-resistant HCMV mutants occurred in vitro, (iii) chemically modified derivatives of ART showed strongly enhanced anti-HCMV efficacy, (iv) NF-κB reporter constructs, upregulated during HCMV replication, could be partially blocked by ART treatment, (v) ART activity analyzed in stable reporter cell clones indicated an inhibition of stimulated NF-κB but not CREB pathway, (vi) solid-phase immobilized ART was able to bind to NF-κB RelA/p65, and (vii) peptides within NF-κB RelA/p65 represent candidates of ART binding as analyzed by in silico docking and mass spectrometry. These novel findings open new prospects for the future medical use of ART and ART-related drug candidates.
Keywords: Artesunate and chemical derivatives; Binding of artesunate to NF-κB RelA/p65; Broad antiviral activity; Human cytomegalovirus; Increase of antiviral efficacy; Interference with NF-κB signaling pathways

The chemical class of quinazoline compounds provides a core structure for the design of anticytomegaloviral kinase inhibitors - Hutterer, Corina; Hamilton, S.; Steingruber, Mirjam; Zeitträger, Isabel; Bahsi, Hanife; Thuma, Natalie; Naing, Z.; Oerfi, Z.; Oerfi, L.; Socher, Eileen; Sticht, Heinrich; Rawlinson, W.; et al. (Antiviral Research, 2016)
HCMV is a member of the family Herpesviridae and represents a worldwide distributed pathogen with seropositivity rates in the adult population ranging between 40% and 90%. Notably, HCMV infection is a serious, sometimes life-threatening medical problem for newborns and immunosuppressed individuals, including transplant recipients and patients under antitumoral chemotherapy. Current standard therapy with valganciclovir has the disadvantage of inducing drug-resistant virus mutants and toxicity-related side effects. Our analysis stresses the earlier finding that kinase inhibitors of the quinazoline class exert an antiviral response by targeting the viral protein kinase pUL97 without inducing resistance. Therefore, quinazolines have been used as a core structure to gain insight in the mode of inhibitor-kinase interaction. Here, we demonstrate that (i) the novel quinazolines Vi7392 and Vi7453 are highly active against HCMV laboratory and clinically relevant strains including maribavir- and ganciclovir-resistant variants, (ii) antiviral activity is not cell-type specific and was also detected in a placental explant tissue model using a genetically intact HCMV strain (iii) the viral kinase pUL97 represents a target of the anticytomegaloviral activity of these compounds, (iv) induction of pUL97-conferring drug resistance was not detectable under single-step selection, thus differed from the induction of ganciclovir resistance, and (v) pUL97 drug docking simulations enabled detailed insights into specific drug-target binding properties providing a promising basis for the design of optimized kinase inhibitors. These novel findings may open new prospects for the future medical use of quinazoline drug candidates and the use of drug-target dynamic simulations for rational design of antivirals.
Keywords: Antiviral drug target; Homology model of pUL97; Human cytomegalovirus; pUL97 drug docking simulation; Quinazoline compounds; Viral kinase pUL97

The complex regulatory role of cytomegalovirus nuclear egress protein pul50 in the production of infectious virus - Häge, Sigrun; Büscher, Nicole; Pakulska, Victoria; Hahn, Friedrich; Adrait, Annie; Krauter, Steffi; Borst, Eva Maria; Schlötzer-Schrehardt, Ursula; Couté, Yohann; Plachter, Bodo; Marschall, Manfred (Cells, 2021)
The regulation of the nucleocytoplasmic release of herpesviral capsids is defined by the process of nuclear egress. Due to their large size, nuclear capsids are unable to traverse via nuclear pores, so that herpesviruses evolved to develop a vesicular transport pathway mediating their transition through both leaflets of the nuclear membrane. This process involves regulatory proteins, which support the local distortion of the nuclear envelope. For human cytomegalovirus (HCMV), the nuclear egress complex (NEC) is determined by the pUL50-pUL53 core that initiates multicomponent assembly with NEC-associated proteins and capsids. Hereby, pUL50 serves as a multi-interacting determinant that recruits several viral and cellular factors by direct and indirect con-tacts. Recently, we generated an ORF-UL50-deleted recombinant HCMV in pUL50-complementing cells and obtained first indications of putative additional functions of pUL50. In this study, we produced purified ∆UL50 particles under both complementing (∆UL50C) and non-complementing (∆UL50N) conditions and performed a phenotypical characterization. Findings were as follows: (i) ∆UL50N particle preparations exhibited a clear replicative defect in qPCR-based infection kinetics compared to ∆UL50C particles; (ii) immuno-EM analysis of ∆UL50C did not reveal major changes in nuclear distribution of pUL53 and lamin A/C; (iii) mass spectrometry-based quantitative proteomics showed a large concordance of protein contents in the NIEP fractions of ∆UL50C and ∆UL50N particles, but virion fraction was close to the detection limit for ∆UL50N; (iv) confocal imaging of viral marker proteins of immediate early (IE) and later phases of ∆UL50N infection indicated a very low number of cells showing an onset of viral lytic protein expression; and, finally (v) quantitative measurements of encapsidated genomes provided evidence for a substantial reduction in the DNA contents in ∆UL50N compared to ∆UL50C particles. In summary, the results point to a complex and important regulatory role of the HCMV nuclear egress protein pUL50 in the maturation of infectious virus.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Conditional expression; Efficiency of infectious virus production; Functional properties; Human cytomegalovirus; NEC protein pUL50; Nuclear egress complex (NEC); Regulation of viral replication

The conserved core nuclear egress complex (NEC) as an antiherpesviral drug target: Pharmacophore-based identification of NEC-specific inhibitors - Tillmanns, Julia; Battisti, Verena; Kicuntod, Jintawee; Hahn, Friedrich; Obergfäll, Debora; Geiger, Pia; Wagner, Sabrina; Buschmann, Helmut; Lesch, Bernhard; Lischka, Peter; Sticht, Heinrich; Langer, Thierry; et al. (Antiviral Research, 2025)
The nucleocytoplasmic capsid egress of herpesviruses is a uniquely regulated process. As well-established for the human cytomegalovirus (HCMV) core nuclear egress complex (NEC), the pUL50–pUL53 NEC heterodimer oligomerizes and builds hexameric lattices for the regulated nucleocytoplasmic release of viral capsids. Recently, we and others validated the NEC as a novel target for antiviral strategies. So far, the experimental targeting approaches included the development of NEC-directed small molecules, cell-penetrating peptides, NEC-specific mutagenesis, and the expression of NEC-interfering protein constructs. Our current postulate states that a small molecule-mediated interference with the assembly of the core NEC prevents NEC-dependent egress regulation and thereby strictly limits viral replication. Here, we present an experimental proof of this antiviral strategy, and the data provide evidence for the following points: (i) pharmacophore-based approaches demonstrated to be successful in the identification of NEC-specific inhibitory small molecules, (ii) already a low number of 36 analyzed small molecules yielded eight experimental hits with micromolar to submicromolar antiviral activity, (iii) their antiviral potency was asserted to the predicted NEC-interfering mode-of-action, (iv) two identified hit compounds presented a broad antiherpesviral activity, and (v) a further pharmacophore-assisted refinement of NEC-directed molecules may lead to the development of highly effective and even broadly acting antivirals. Combined, we strengthen the recently postulated potential of the NEC as a next-generation antiherpesviral drug target by identifying broadly active NEC inhibitors via a pharmacophore-based approach.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Conserved viral nuclear egress complex (NEC); Human pathogenic herpesvirus infections; NEC-Directed antiviral drugs; Novel concept of broadly acting antivirals; Novel drug targeting options; Pharmacophore-based hit identification; α-; β-; γ-herpesviruses

The crystal structure of the varicella-zoster Orf24-Orf27 nuclear egress complex spotlights multiple determinants of herpesvirus subfamily specificity - Schweininger, Johannes; Kriegel, Mark; Häge, Sigrun; Conrad, Marcus; Alkhashrom, Sewar; Lösing, Josephine; Weiler, Sigrid; Tillmanns, Julia; Egerer-Sieber, Claudia; Decker, Andrea; Rovis, Tihana Lenac; Eichler, Jutta; et al. (Journal of Biological Chemistry, 2022)
Varicella-zoster virus (VZV) is a human pathogen from the α-subfamily of herpesviruses. The VZV Orf24-Orf27 complex represents the essential viral core nuclear egress complex (NEC) that orchestrates the egress of the preassembled virus capsids from the nucleus. While previous studies have primarily emphasized that the architecture of core NEC complexes is highly conserved among herpesviruses, the present report focuses on subfamily-specific structural and functional features that help explain the differences in the autologous versus nonautologous interaction patterns observed for NEC formation across herpesviruses. Here, we describe the crystal structure of the Orf24-Orf27 complex at 2.1 Å resolution. Coimmunoprecipitation and confocal imaging data show that Orf24-Orf27 complex formation displays some promiscuity in a herpesvirus subfamily-restricted manner. At the same time, analysis of thermodynamic parameters of NEC formation of three prototypical α-, β-, and γ herpesviruses, i.e., VZV, human cytomegalovirus (HCMV), and Epstein-Barr virus (EBV), revealed highly similar binding affinities for the autologous interaction with specific differences in enthalpy and entropy. Computational alanine scanning, structural comparisons, and mutational data highlight intermolecular interactions shared among α-herpesviruses that are clearly distinct from those seen in β- and γ-herpesviruses, including a salt bridge formed between Orf24-Arg167 and Orf27-Asp126. This interaction is located outside of the hook-into-groove interface and contributes significantly to the free energy of complex formation. Combined, these data explain distinct properties of specificity and permissivity so far observed in herpesviral NEC interactions. These findings will prove valuable in attempting to target multiple herpesvirus core NECs with selective or broadacting drug candidates.
CRIS-Team Scopus Importer:2022-03-04

The cyclin-dependent kinase ortholog pUL97 of human cytomegalovirus interacts with cyclins - Graf, Laura; Webel, Rike; Wagner, Sabrina; Hamilton, Stuart T.; Rawlinson, William D.; Sticht, Heinrich; Marschall, Manfred (Viruses, 2013)
The human cytomegalovirus (HCMV)-encoded protein kinase, pUL97, is considered a cyclin-dependent kinase (CDK) ortholog, due to shared structural and functional characteristics. The primary mechanism of CDK activation is binding to corresponding cyclins, including cyclin T1, which is the usual regulatory cofactor of CDK9. This study provides evidence of direct interaction between pUL97 and cyclin T1 using yeast two-hybrid and co-immunoprecipitation analyses. Confocal immunofluorescence revealed partial colocalization of pUL97 with cyclin T1 in subnuclear compartments, most pronounced in viral replication centres. The distribution patterns of pUL97 and cyclin T1 were independent of HCMV strain and host cell type. The sequence domain of pUL97 responsible for the interaction with cyclin T1 was between amino acids 231-280. Additional co-immunoprecipitation analyses showed cyclin B1 and cyclin A as further pUL97 interaction partners. Investigation of the pUL97-cyclin T1 interaction in an ATP consumption assay strongly suggested phosphorylation of pUL97 by the CDK9/cyclin T1 complex in a substrate concentration-dependent manner. This is the first demonstration of interaction between a herpesviral CDK ortholog and cellular cyclins.
EVALuna2:8102

The cytomegalovirus egress proteins pUL50 and pUL53 are translocated to the nuclear envelope through two distinct modes of nuclear import - Schmeiser, Cathrin; Borst, Eva; Sticht, Heinrich; Marschall, Manfred; Milbradt, Jens (Journal of General Virology, 2013)
The nucleocytoplasmic export of cytomegaloviral capsids is regulated by formation of a multi-component nuclear egress complex (NEC), essentially based on viral proteins pUL50 and pUL53. In this study, the generation of recombinant human cytomegaloviruses, expressing tagged versions of pUL50 and pUL53, enabled the investigation of NEC formation in infected primary fibroblasts. For these recombinant viruses, a wild-type-like mode of pUL50-pUL53 interaction and recruitment of both proteins to the nuclear envelope could be demonstrated. Importantly, pUL50 was translocated from an initial cytoplasmic distribution to the nuclear rim, whereas pUL53 accumulated in the nucleus before attaining overall rim colocalization with pUL50. Specified experimental settings illustrated that pUL50 and pUL53 were subject to different pathways of intracellular trafficking. Importantly, a novel nuclear localization signal (NLS) could be identified and functionally verified for pUL53 (amino acids 18-27), whereas no NLS was present in pUL50. Analysis of amino acid replacement mutants further illustrated the differential modes of nuclear import of the two essential viral egress proteins. Taken together, our findings suggest a combination of classical nuclear import (pUL53) and interaction-mediated recruitment (pUL50) as the driving forces for core NEC formation and viral nuclear egress.
EVALuna2:8188

The cytomegalovirus protein kinase pUL97: Host interactions, regulatory mechanisms and antiviral drug targeting - Steingruber, Mirjam; Marschall, Manfred (Microorganisms, 2020)
Human cytomegalovirus (HCMV) expresses a variety of viral regulatory proteins that undergo close interaction with host factors including viral-cellular multiprotein complexes. The HCMV protein kinase pUL97 represents a viral cyclin-dependent kinase ortholog (vCDK) that determines the efficiency of HCMV replication via phosphorylation of viral and cellular substrates. A hierarchy of functional importance of individual pUL97-mediated phosphorylation events has been discussed; however, the most pronounced pUL97-dependent phenotype could be assigned to viral nuclear egress, as illustrated by deletion of the UL97 gene or pharmacological pUL97 inhibition. Despite earlier data pointing to a cyclin-independent functionality, experimental evidence increasingly emphasized the role of pUL97-cyclin complexes. Consequently, the knowledge about pUL97 involvement in host interaction, viral nuclear egress and additional replicative steps led to the postulation of pUL97 as an antiviral target. Indeed, validation experiments in vitro and in vivo confirmed the sustainability of this approach. Consequently, current investigations of pUL97 in antiviral treatment go beyond the known pUL97-mediated ganciclovir prodrug activation and henceforward include pUL97-specific kinase inhibitors. Among a number of interesting small molecules analyzed in experimental and preclinical stages, maribavir is presently investigated in clinical studies and, in the near future, might represent a first kinase inhibitor applied in the field of antiviral therapy.
CRIS-Team Scopus Importer:2020-04-24
Keywords: Antiviral drugs; Cyclin/cyclin-dependent kinase complexes; Human cytomegalovirus (HCMV); Kinase-host interactions; Protein kinase pUL97; Regulatory mechanisms

The human cytomegalovirus nuclear egress complex unites multiple functions: Recruitment of effectors, nuclear envelope rearrangement, and docking to nuclear capsids - Marschall, Manfred; Muller, Yves; Diewald, Benedikt; Sticht, Heinrich; Milbradt, Jens (Reviews in Medical Virology, 2017)
Keywords: antiviral drugs; capsid-NEC docking; herpesviruses; human cytomegalovirus; nuclear egress complex

The interaction between cyclin B1 and cytomegalovirus protein kinase pUL97 is determined by an active kinase domain - Steingruber, Mirjam; Socher, Eileen; Hutterer, Corina; Webel, Rike; Bergbrede, Tim; Lenac, Tihana; Sticht, Heinrich; Marschall, Manfred (Viruses, 2015)
Replication of human cytomegalovirus (HCMV) is characterized by a tight virus-host cell interaction. Cyclin-dependent protein kinases (CDKs) are functionally integrated into viral gene expression and protein modification. The HCMV-encoded protein kinase pUL97 acts as a CDK ortholog showing structural and functional similarities. Recently, we reported an interaction between pUL97 kinase with a subset of host cyclins, in particular with cyclin T1. Here, we describe an interaction of pUL97 at an even higher affinity with cyclin B1. As a striking feature, the interaction between pUL97 and cyclin B1 proved to be strictly dependent on pUL97 activity, as interaction could be abrogated by treatment with pUL97 inhibitors or by inserting mutations into the conserved kinase domain or the nonconserved C-terminus of pUL97, both producing loss of activity. Thus, we postulate that the mechanism of pUL97-cyclin B1 interaction is determined by an active pUL97 kinase domain.
Keywords: Active conformation; CDK ortholog; Cyclin B; Human cytomegalovirus; Kinase activity; Mode of kinase-cyclin interaction; Protein kinase pUL97; Protein-protein interaction

The Interactive Complex between Cytomegalovirus Kinase vCDK/pUL97 and Host Factors CDK7-Cyclin H Determines Individual Patterns of Transcription in Infected Cells. - Schütz, Martin; Cordsmeier, Arne; Wangen, Christina; Horn, Anselm; Wyler, Emanuel; Enßer, Armin; Sticht, Heinrich; Marschall, Manfred (International Journal of Molecular Sciences, 2023)
The infection of human cytomegalovirus (HCMV) is strongly determined by the host-cell interaction in a way that the efficiency of HCMV lytic replication is dependent on the regulatory interplay between viral and cellular proteins. In particular, the activities of protein kinases, such as cyclin-dependent kinases (CDKs) and the viral CDK ortholog (vCDK/pUL97), play an important role in both viral reproduction and virus-host interaction. Very recently, we reported on the complexes formed between vCDK/pUL97, human cyclin H, and CDK7. Major hallmarks of this interplay are the interaction between cyclin H and vCDK/pUL97, which is consistently detectable across various conditions and host cell types of infection, the decrease or increase in pUL97 kinase activity resulting from cyclin H knock-down or elevated levels, respectively, and significant trans-stimulation of human CDK7 activity by pUL97 in vitro. Due to the fact that even a ternary complex of vCDK/pUL97-cyclin H-CDK7 can be detected by coimmunoprecipitation and visualized by bioinformatic structural modeling, we postulated a putative impact of the respective kinase activities on the patterns of transcription in HCMV-infected cells. Here, we undertook a first vCDK/pUL97-specific transcriptomic analysis, which combined conditions of fully lytic HCMV replication with those under specific vCDK/pUL97 or CDK7 drug-mediated inhibition or transient cyclin H knockout. The novel results were further strengthened using bioinformatic modeling of the involved multi-protein complexes. Our data underline the importance of these kinase activities for the C-terminal domain (CTD) phosphorylation-driven activation of host RNA polymerase in HCMV-infected cells. The impact of the individual experimental conditions on differentially expressed gene profiles is described in detail and discussed.
EVALuna2:545510

The Oligomeric Assemblies of Cytomegalovirus Core Nuclear Egress Proteins Are Associated with Host Kinases and Show Sensitivity to Antiviral Kinase Inhibitors - Kicuntod, Jintawee; Häge, Sigrun; Hahn, Friedrich; Sticht, Heinrich; Marschall, Manfred (Viruses, 2022)
The nucleo-cytoplasmic capsid egress of herpesviruses is a unique regulated process that ensures the efficiency of viral replication and release. For human cytomegalovirus (HCMV), the core of the nuclear egress complex (NEC) consists of the pUL50–pUL53 heterodimer that is able to oligomerize and thus to build hexameric lattices. These structures determine capsid binding and multicomponent protein interaction including NEC-associated host factors. The underlying characteristic of the core NEC formation is based on the N-terminal hook structure of pUL53 that binds into an alpha-helical groove of pUL50, and is thus described as a hook-into-groove interaction. This central regulatory element has recently been validated as a target of antiviral strategies, and first NEC-targeted prototypes of inhibitory small molecules were reported by our previous study. Here, we further analyzed the oligomerization properties of the viral NEC through an approach of chemical protein cross-linking. Findings were as follows: (i) a cross-link approach demonstrated the oligomeric state of the HCMV core NEC using material from HCMV-infected or plasmid-transfected cells, (ii) a Western blot-based identification of NEC-associated kinases using the cross-linked multicomponent NECs was successful, and (iii) we demonstrated the NEC-inhibitory and antiviral activity of specific inhibitors directed to these target kinases. Combined, the results strongly underline the functional importance of the oligomerization of the HCMV-specific NEC that is both phosphorylation-dependent and sensitive to antiviral kinase inhibitors.
CRIS-Team Scopus Importer:2022-06-03
Keywords: associated protein kinases; core NEC pUL50-pUL53; cross-linking; cyclin-dependent kinases (CDKs); human cytomegalovirus; kinase inhibitors; NEC as an antiviral target; NEC-inhibitory potential; nuclear egress complex (NEC); oligomerization; viral nucleocytoplasmic egress

The peptidyl-prolyl cis/trans isomerase Pin1 interacts with three early regulatory proteins of human cytomegalovirus - Schütz, Martin; Thomas, Marco; Wangen, Christina; Wagner, Sabrina; Rauschert, Luisa; Errerd, Theresa; Kießling, Melissa; Sticht, Heinrich; Milbradt, Jens; Marschall, Manfred (Virus Research, 2020)
Human cytomegalovirus (HCMV) is a ubiquitous human pathogen of high clinical relevance. Despite intensive research of virus-host interaction, crucial details still remain unknown. In this study, the role of the cellular peptidyl-prolyl cis/trans isomerase Pin1 during HCMV infection was investigated. Pin1 is able to recognize phosphorylated serine/threonine-proline motifs and regulates the structural conformation, stability and function of its substrates. Concerning HCMV replication, our recent studies revealed that Pin1 plays an important role in viral nuclear egress by contributing to the depletion of the nuclear lamina at distinct sites through the cis/trans conversion of lamin proteins. Here, novel data illustrate the HCMV-induced upregulation of Pin1 including various cell types being permissive, semi-permissive or non-permissive for productive HCMV replication. Addressing the question of functional impact, Pin1 knock-out (KO) did not show a measurable effect on viral protein expression, at least when assessed by Western blot analysis. Applying highly sensitive methods of qPCR and plaque titration, a pharmacological inhibition of Pin1 activity, however, led to a significant decrease of viral genome equivalents and production of infectious virus, respectively. When focusing on the identification of viral proteins interacting with Pin1 by various coimmunoprecipitation (CoIP) settings, we obtained positive signals for (i) the core nuclear egress complex protein pUL50, (ii) the viral mRNA export factor pUL69 and (iii) the viral DNA polymerase processivity factor pUL44. Confocal immunofluorescence analysis focusing on partial colocalization between Pin1 and the coexpressed viral proteins pUL50, pUL69 or pUL44, respectively, was consistent with the CoIP experiments. Mapping experiments, using transient expression constructs for a series of truncated protein versions and specific replacement mutants, revealed a complex pattern of Pin1 interaction with these three early regulatory HCMV proteins. Data suggest a combination of different modes of Pin1 interactions, involving both classical phosphorylation-dependent Pin1 binding motifs and additional phosphorylation-independent binding sites. Combined, these results support the concept that Pin1 may play an important role in several stages of HCMV infection, thus determining viral replicative efficiency.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Cytomegalovirus replication; Phosphorylation-independent interaction; Pin1 inhibitor-mediated viral replication block; Pin1 interaction with pUL50; Pin1 upregulation; Prolyl cis/trans isomerase Pin1; pUL44; pUL69

The Prolyl Isomerase Pin1 Promotes the Herpesvirus-Induced Phosphorylation-Dependent Disassembly of the Nuclear Lamina Required for Nucleocytoplasmic Egress - Milbradt, Jens; Hutterer, Corina; Bahsi, Hanife; Wagner, Sabrina; Sonntag, Ellen; Horn, Anselm; Kaufer, Benedikt B.; Mori, Yasuko; Sticht, Heinrich; Fossen, Torgils; Marschall, Manfred (PLoS Pathogens, 2016)
The nuclear lamina lines the inner nuclear membrane providing a structural framework for the nucleus. Cellular processes, such as nuclear envelope breakdown during mitosis or nuclear export of large ribonucleoprotein complexes, are functionally linked to the disassembly of the nuclear lamina. In general, lamina disassembly is mediated by phosphorylation, but the precise molecular mechanism is still not completely understood. Recently, we suggested a novel mechanism for lamina disassembly during the nuclear egress of herpesviral capsids which involves the cellular isomerase Pin1. In this study, we focused on mechanistic details of herpesviral nuclear replication to demonstrate the general importance of Pin1 for lamina disassembly. In particular, Ser22-specific lamin phosphorylation consistently generates a Pin1-binding motif in cells infected with human and animal alpha-, beta-, and gammaherpesviruses. Using nuclear magnetic resonance spectroscopy, we showed that binding of Pin1 to a synthetic lamin peptide induces its cis/trans isomerization in vitro. A detailed bioinformatic evaluation strongly suggests that this structural conversion induces large-scale secondary structural changes in the lamin N-terminus. Thus, we concluded that a Pin1-induced conformational change of lamins may represent the molecular trigger responsible for lamina disassembly. Consistent with this concept, pharmacological inhibition of Pin1 activity blocked lamina disassembly in herpesvirus-infected fibroblasts and consequently impaired virus replication. In addition, a phospho-mimetic Ser22Glu lamin mutant was still able to form a regular lamina structure and overexpression of a Ser22-phosphorylating kinase did not induce lamina disassembly in Pin1 knockout cells. Intriguingly, this was observed in absence of herpesvirus infection proposing a broader importance of Pin1 for lamina constitution. Thus, our results suggest a functional model of similar events leading to disassembly of the nuclear lamina in response to herpesviral or inherent cellular stimuli. In essence, Pin1 represents a regulatory effector of lamina disassembly that promotes the nuclear pore-independent egress of herpesviral capsids.
EVALuna2:8308

The Trimeric Artesunate Analog TF27, a Broadly Acting Anti-Infective Model Drug, Exerts Pronounced Anti-SARS-CoV-2 Activity Spanning Variants and Host Cell Types - Hahn, Friedrich; Wangen, Christina; Häge, Sigrun; Herrmann, Lars; Herrmann, Alexandra; Tsogoeva, Svetlana; Marschall, Manfred (Pharmaceutics, 2023)
Starting in 2019, the spread of respiratory syndrome coronavirus 2 (SARS-CoV-2) and the associated pandemic of the corona virus disease (COVID-19) has led to enormous efforts in the development of medical countermeasures. Although innovative vaccines have scaled back the number of severe COVID cases, the emergence of the omicron variant (B.1.1.529) illustrates how vaccine development struggles to keep pace with viral evolution. On the other hand, while the recently approved antiviral drugs remdesivir, molnupiravir, and Paxlovid are considered as broadly acting anti-coronavirus therapeutics, only molnupiravir and Paxlovid are orally available and none of these drugs are recommended for prophylactic use. Thus, so far unexploited small molecules, targeting strategies, and antiviral mechanisms are urgently needed to address issues in the current pandemic and in putative future outbreaks of newly emerging variants of concern. Recently, we and others have described the anti-infective potential and particularly the pronounced antiviral activity of artesunate and related compounds of the trioxane/sesquiterpene class. In particular, the trimeric derivative TF27 demonstrated strong anti-cytomegalovirus activity at nanomolar concentrations in vitro as well as in vivo efficacy after oral administration in therapeutic and even prophylactic treatment settings. Here, we extended this analysis by evaluating TF27 for its anti-SARS-CoV-2 potential. Our main findings are as follows: (i) compound TF27 exerted strong anti-SARS-CoV-2 activity in vitro (EC50 = 0.46 ± 0.20 µM), (ii) antiviral activity was clearly distinct from the induction of cytotoxicity, (iii) pretreatment with TF27 prevented virus replication in cultured cells, (iv) antiviral activity has likewise been demonstrated in Calu-3 human lung and Caco-2 human colon cells infected with wild-type, delta, or omicron SARS-CoV-2, respectively, and (v) analysis of TF27 combination treatments has revealed synergistic interaction with GC376, but antagonistic interaction with EIDD-1931. Combined, the data demonstrated the pronounced anti-SARS-CoV-2 activity of TF27 and thus highlight the potential of trioxane compounds for further pharmacologic development towards improved options for COVID-specific medication.
CRIS-Team Scopus Importer:2023-02-03
Keywords: artesunate and analogs; broad-spectrum inhibitory properties; host-directed drug targeting; pronounced anti-SARS-CoV-2 activity; SARS-CoV-2 infection; trimeric analog TF27